Fiber-reinforced polyamide resin composition, molded body, sliding member, gear, worm wheel, and method for producing thermoplastic resin composition
By optimizing the composition and manufacturing method of the fiber-reinforced polyamide resin composition, the problems of insufficient mechanical properties, physical properties and sliding characteristics of the polyamide resin in the prior art are solved, high mechanical properties, low physical properties and vibration fatigue resistance are achieved, and the coloring of the finished resin product is suppressed.
Patent Information
- Application Number
- CN202380053655.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-14
- Filing Date
- 2023-07-14
- Publication Date
- 2025-03-07
AI Technical Summary
The prior art has shortcomings in improving the mechanical properties of polyamide resins, reducing physical properties changes and imparting sliding characteristics. Especially when the filler is included, vibration fatigue resistance is insufficient, and the finished resin product is prone to coloring, affecting the tone and transparency.
Using a fiber-reinforced polyamide resin composition containing crystalline polyamide and glass fiber, the composition and manufacturing method of the composition, including melt kneading and heating steps, is optimized by specific formic acid relative viscosity and length and diameter ratios of glass fibers, to improve the mechanical properties of the resin and vibration fatigue resistance while inhibiting coloring.
The mechanical properties and sliding characteristics of the fiber-reinforced polyamide resin composition are improved, and the physical properties change is reduced, vibration fatigue resistance is improved, and the coloring of the finished resin product is suppressed, and the coloring and coloring are improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to a fiber-reinforced polyamide resin composition having excellent wear properties and mechanical properties, and a molded product comprising the fiber-reinforced polyamide resin composition. More specifically, the present invention relates to a fiber-reinforced polyamide resin composition characterized by comprising a polyamide having a specific viscosity and glass fibers of a specific composition, and a molded product, a sliding component, a gear, and a worm wheel comprising the fiber-reinforced polyamide resin composition.
[0002] Furthermore, the present invention relates to a method for producing a thermoplastic resin composition.
[0003] This application claims priority based on Japanese Patent Application No. 2022-113784 filed in Japan on July 15, 2022, Japanese Patent Application No. 2022-122261 filed in Japan on July 29, 2022, and Japanese Patent Application No. 2022-165824 filed in Japan on October 14, 2022, the contents of which are incorporated herein by reference. Background Art
[0004] Polyamide resins have excellent sliding properties, molding processability, mechanical properties, and chemical resistance, and therefore have been widely used as various component materials for industrial materials, automobiles, electrical and electronic applications, and industrial applications.
[0005] In particular, polyamide resins are often used as sliding members such as gears and worms for automobiles from the viewpoint of excellent sliding properties and mechanical characteristics.
[0006] In order to improve these properties, studies have been conducted on compositions having a higher viscosity than that of ordinary polyamides or composite compositions with inorganic compound fillers such as glass fibers, flaky glass, alumina fibers, and layered inorganic compounds.
[0007] Among them, a glass fiber-reinforced polyamide resin composition containing a high molecular weight polyamide and using glass fibers as an inorganic compound filler has attracted particular attention because of its high effect of improving sliding properties and mechanical characteristics.
[0008] On the other hand, since the automobile itself is required to be lightweight from the perspective of environmental protection, there is also a demand for miniaturization of sliding components such as automobile gears and worms. Along with this, it is required to improve the durability of the material itself of the sliding component and reduce the variation of the physical properties of the small component.
[0009] Regarding glass fiber reinforced polyamide resin compositions including high molecular weight polyamide compositions, for example, Patent Documents 1 and 2 disclose compositions capable of improving sliding properties, mechanical properties, and productivity by blending specific glass fibers and coupling agents.
[0010] On the other hand, in recent years, there has been an increasing demand for resin compositions having a high molecular weight resin component in order to improve the performance of various machines and parts.
[0011] As methods for obtaining a high molecular weight resin composition, there are known methods of melt-kneading a high molecular weight resin using an extruder; a method of melt-kneading a low molecular weight resin using an extruder to obtain a granular material, and then performing a heating step (hereinafter sometimes referred to as solid phase polymerization) to increase the molecular weight, etc.
[0012] Patent document 3 describes a continuous solid phase polymerization method for nylon 66, in which nylon 66 chips crystallized in such a way that the crystallinity of the chip surface is 11% or more are caused to flow down in a layered manner, and solid phase polymerization is carried out by heating to 150° C. to 200° C. using an inert gas supplied countercurrently from below.
[0013] Patent document 4 describes a method for producing polyamide resin chips, wherein, after a solid phase polymerization step in which raw material polyamide resin chips are deposited while being moved by free fall and an inert gas is conveyed countercurrently to the movement of the raw material polyamide resin chips, an operation is performed in which the dew point of the inert gas is corrected to maintain the water content of the polyamide resin chips within a specified range during a step of cooling the polyamide resin chips under an inert gas in a cooling zone.
[0014] Patent document 5 describes a reinforced polyamide resin pellet containing a polyamide resin having a melting point of 200°C to 270°C and at least one inorganic filler selected from the group consisting of chopped strand glass fiber, carbon fiber, wollastonite, talc, mica, kaolin, barium sulfate, calcium carbonate, apatite, sodium phosphate, fluorite, silicon nitride, potassium titanate, and molybdenum disulfide, and the ratio of the major axis to the minor axis of the cross section (major axis / minor axis) is 1.3 to 2.5.
[0015] Patent Document 6 describes a resin composition pellet containing a thermoplastic resin and a desiccant and having an elliptical column shape, wherein the ratio of the minor axis to the major axis (minor axis / major axis) of the elliptical surface of the pellet is 0.5 to 0.9.
[0016] Alternatively, various fillers have been added to the polyamide resin to improve the mechanical properties of the polyamide resin molded product or the molding properties of the polyamide resin. Examples of such fillers include tetrafluoroethylene resin particles as a lubricant and glass fibers as a reinforcing material.
[0017] Patent Document 7 describes a polyamide resin composition suitable for molding sliding members having low friction and excellent wear resistance, which is obtained by blending polytetrafluoroethylene particles and, if necessary, calcium titanate whiskers, glass fibers, etc., into a polyamide resin represented by nylon 46.
[0018] Patent Document 8 describes a resin composition for a sliding material formed by blending glass fiber, tetrafluoroethylene resin, and molybdenum disulfide into a polyamide resin represented by nylon 66 (polyamide resin 66).
[0019] Patent Document 9 describes a resin composition obtained by blending 15% by mass or more and 30% by mass or less of reinforcing fibers such as glass fibers having a fiber diameter of about 6 μm or more and about 8 μm or less into a thermoplastic resin represented by nylon MXD6 and nylon 66. Patent Document 9 describes that the resin composition is particularly suitable for producing a hollow tube having excellent inner surface smoothness.
[0020] Patent Document 10 describes a reduction gear for an electric power steering device molded from a polyamide resin mixture. Patent Document 4 discloses that a fibrous material such as glass fiber or carbon fiber is blended into a polyamide resin mixture.
[0021] Patent Document 11 discloses the results of studying various physical properties centered on the above-mentioned wear resistance, friction characteristics and limiting PV value for molded products of polyamide resin compositions containing glass fibers known to date. Specifically, Patent Document 11 reports that when a polyamide resin composition formed by blending polyamide 66 having a number average molecular weight within a specific range, glass fibers having a specific average fiber diameter and average fiber length that are bundled using a specific sizing agent, and specific additives is molded, particularly excellent wear resistance, friction characteristics and limiting PV value are achieved.
[0022] Prior art literature
[0023] Patent Literature
[0024] Patent Document 1: Japanese Patent Application Publication No. 2018-197316
[0025] Patent Document 2: Japanese Patent Application Publication No. 2016-117817
[0026] Patent Document 3: Japanese Patent Application Publication No. 2000-198841
[0027] Patent Document 4: Japanese Patent Application Publication No. 2016-69515
[0028] Patent Document 5: Japanese Patent Application Publication No. 2016-14154
[0029] Patent Document 6: International Publication No. 2017 / 111055
[0030] Patent Document 7: Japanese Patent Application Laid-Open No. 62-185747
[0031] Patent Document 8: Japanese Patent Application Laid-Open No. 1-110558
[0032] Patent Document 9: Japanese Patent Application Laid-Open No. 8-41246
[0033] Patent Document 10: Japanese Patent Application Publication No. 2003-83423
[0034] Patent Document 11: Japanese Patent No. 4321590 Summary of the invention
[0035] Problems to be solved by the invention
[0036] However, in Patent Documents 1 and 2, sufficient mechanical properties, reduction of property variation, and sliding properties are not achieved for polyamides in a high molecular weight region having a formic acid relative viscosity of 90 or more, and further improvement is desired.
[0037] Patent Documents 3 and 4 are technologies regarding a solid phase polymerization method of chips (pellets), and Patent Documents 5 and 6 are technologies regarding the shape of pellets. Therefore, no research has been conducted on the shape of pellets used in solid phase polymerization of thermoplastic resins such as polyamide resins.
[0038] On the other hand, in general, in the case of a resin that is not reinforced with a filler, vibration fatigue characteristics are controlled by entanglement of polymer chains, so that the vibration fatigue resistance of the polymer is improved.
[0039] On the other hand, in the case of a resin reinforced with a filler, the interface between the filler and the resin may become a starting point of vibration fatigue fracture. If the adhesion between the interface between the filler and the resin is low, the vibration fatigue resistance is reduced.
[0040] Therefore, although the polyamide resin compositions described in Patent Documents 7 to 11 have sufficiently high molecular weights, they contain fillers and therefore have a problem of being insufficient in terms of vibration fatigue resistance.
[0041] In addition, as a characteristic of polyamide resin, the polymer is easily colored yellow due to thermal oxidation degradation, so the resin pellets are colored, the color tone and transparency of the obtained resin molded products are poor, and the commercial value is also reduced. Therefore, it is strongly desired to obtain products with excellent color tone quality.
[0042] The present invention has been made in view of the above problems, and its object is to provide a fiber-reinforced polyamide resin composition having sufficient mechanical properties, reduced property variations, and sliding characteristics, and a molded body, a sliding member, a gear, and a worm wheel using the fiber-reinforced polyamide resin composition.
[0043] Another object of the present invention is to provide a method for producing a thermoplastic resin composition that achieves improvements in mechanical properties, long-term properties, and productivity.
[0044] Another object of the present invention is to provide a method for producing a thermoplastic resin composition capable of improving vibration fatigue resistance and suppressing coloration.
[0045] Means used to solve problems
[0046] The present invention includes the following aspects.
[0047] [1] A fiber-reinforced polyamide resin composition comprising a crystalline polyamide (A1) and glass fibers (B1), wherein the fiber-reinforced polyamide resin composition has a formic acid relative viscosity of 90 or more, an insoluble component when the fiber-reinforced polyamide resin composition is dissolved in formic acid is 105% by mass or more relative to the ash content of the fiber-reinforced polyamide resin composition, and a ratio of glass fibers having a fiber length of 250 μm or less in the glass fibers (B1) contained in the fiber-reinforced polyamide resin composition is 55% or less.
[0048] [2] The fiber-reinforced polyamide resin composition according to [1], wherein the glass fiber has a number average fiber diameter of 5 μm or more and 9 μm or less.
[0049] [3] The fiber-reinforced polyamide resin composition according to [1] or [2], wherein the fiber-reinforced polyamide resin composition contains 1 part by mass or more and 100 parts by mass or less of the glass fiber (B1) relative to 100 parts by mass of the crystalline polyamide (A1).
[0050] [4] The fiber-reinforced polyamide resin composition according to any one of [1] to [3], wherein the fiber-reinforced polyamide resin composition has a formic acid relative viscosity of 130 or more.
[0051] [5] A molded product obtained by molding the fiber-reinforced polyamide resin composition according to any one of [1] to [4].
[0052] [6] A sliding member comprising the fiber-reinforced polyamide resin composition according to any one of [1] to [4].
[0053] [7] The sliding member according to [6], wherein the coefficient of variation of the tensile strength of the sliding member measured in accordance with ISO527 is 1.0 or less.
[0054] [8] A gear comprising the fiber-reinforced polyamide resin composition according to any one of [1] to [4].
[0055] [9] A worm wheel comprising the fiber-reinforced polyamide resin composition according to any one of [1] to [4].
[0056]
[10] A method for producing a thermoplastic resin composition, characterized in that the method comprises the following steps:
[0057] a melt-kneading step of adding 5 parts by mass or more and 100 parts by mass or less of glass fibers having an average fiber diameter of 3 μm or more and 15 μm or less to 100 parts by mass of a thermoplastic resin having a viscosity number RV of 25 or more and 70 or less, and melt-kneading the mixture to obtain a melt-kneaded product; and
[0058] A heating step, wherein the melt-kneaded product is heated at a temperature T represented by the following formula (I), thereby obtaining a thermoplastic resin composition;
[0059] The melt-kneaded product is an elliptical column-shaped pellet, and the ratio a / b of the major diameter a to the minor diameter b of the cross section of the elliptical column-shaped pellet is 1.3 to 3.0.
[0060] In the heating step, the elliptical columnar pellets are heated while being stirred.
[0061] Tm-130℃≤T≤Tm-10℃ (I)
[0062] (wherein Tm is the melting point of the thermoplastic resin).
[0063]
[11] The method for producing a thermoplastic resin composition according to
[10] above, wherein the viscosity number RV of the thermoplastic resin is 70 or more and 400 or less.
[0064]
[12] The method for producing a thermoplastic resin composition according to
[10] or
[11] above, wherein in the heating step, heating at the temperature T is performed for 30 minutes to 15 hours.
[0065]
[13] The method for producing a thermoplastic resin composition according to any one of
[10] to
[12] above, wherein the thermoplastic resin is polyamide or polyester.
[0066]
[14] The method for producing a thermoplastic resin composition according to
[13] above, wherein the polyamide is at least one selected from the group consisting of polyamide 6, polyamide 66, polyamide 46, polyamide 610 and polyamide 612.
[0067]
[15] The method for producing a thermoplastic resin composition according to any one of
[10] to
[14] above, wherein in the heating step, the heating at the temperature T is performed in an inert gas atmosphere having an oxygen concentration of 5 ppm or less.
[0068]
[16] The method for producing a thermoplastic resin composition according to any one of
[10] to
[15] above, wherein in the heating step, the heating at the temperature T is performed in an inert gas atmosphere having a water concentration of 10 ppm or less.
[0069]
[17] A method for producing a thermoplastic resin composition, characterized in that the method comprises the following steps:
[0070] a melt-kneading step of adding 5 parts by mass or more and 100 parts by mass or less of glass fibers having an average fiber diameter of 3 μm or more and 9 μm or less to 100 parts by mass of a thermoplastic resin having a viscosity number VN of 80 or more and 200 or less, and melt-kneading the mixture to obtain a melt-kneaded product; and
[0071] a heating step, wherein the melt-kneaded product is heated at a temperature T represented by the following formula (I) to obtain a thermoplastic resin composition,
[0072] In the heating step, 0.05% by mass to 1.0% by mass of water is contained relative to 100% by mass of the melt-kneaded product obtained in the melt-kneading.
[0073] Tm-130℃≤T≤Tm-10℃ (I)
[0074] (wherein Tm is the melting point of the thermoplastic resin).
[0075]
[18] The method for producing a thermoplastic resin composition according to
[17] , wherein the viscosity number VN of the thermoplastic resin composition is 200 or more and 350 or less.
[0076]
[19] The method for producing a thermoplastic resin composition according to
[17] or
[18] , wherein the average fiber length of the glass fibers contained in the thermoplastic resin composition after the heating step is 100 μm to 1000 μm.
[0077]
[20] The method for producing a thermoplastic resin composition according to any one of
[17] to
[19] , wherein the average fiber diameter of the glass fiber is 4 μm or more and 8 μm or less.
[0078]
[21] The method for producing a thermoplastic resin composition according to any one of
[17] to
[20] , wherein in the heating step, heating at the temperature T is performed for 30 minutes to 15 hours.
[0079]
[22] The method for producing a thermoplastic resin composition according to any one of
[17] to
[21] , wherein in the heating step, the heating at the temperature T is performed in an inert gas atmosphere having an oxygen concentration of 5 ppm or less.
[0080]
[23] The method for producing a thermoplastic resin composition according to any one of
[17] to
[22] , wherein the thermoplastic resin is polyamide or polyester.
[0081]
[24] The method for producing a thermoplastic resin composition according to
[23] , wherein the polyamide is polyamide 6, polyamide 66 or polyamide 610.
[0082]
[25] The method for producing a thermoplastic resin composition according to any one of
[17] to
[24] , wherein the thermoplastic resin composition does not substantially contain boron oxide.
[0083] Effects of the Invention
[0084] According to the present invention, a fiber-reinforced polyamide resin composition having sufficient mechanical properties, reduced property variation, and having sliding characteristics, and a molded product, a sliding member, a gear, and a worm wheel using the fiber-reinforced polyamide resin composition can be obtained.
[0085] According to the present invention, it is possible to provide a method for producing a thermoplastic resin composition that achieves improvements in mechanical properties, long-term properties, and productivity.
[0086] According to the present invention, it is possible to produce a thermoplastic resin composition that can improve vibration fatigue resistance and suppress coloration. DETAILED DESCRIPTION
[0087] Hereinafter, the mode for implementing the present invention will be described in detail. It should be noted that the present invention is not limited to the following embodiments, and can be implemented with various modifications within the scope of the gist thereof.
[0088] <Fiber-reinforced polyamide resin composition>
[0089] The fiber-reinforced polyamide resin composition of the first embodiment of the present invention contains a crystalline polyamide (A1) and a glass fiber (B1). Hereinafter, the "fiber-reinforced polyamide resin composition" may be simply referred to as a "polyamide composition".
[0090] The formic acid relative viscosity VR of the fiber-reinforced polyamide resin composition is not less than 90. When the formic acid relative viscosity is not less than 90, there is a tendency to obtain a fiber-reinforced polyamide resin molded body having more excellent mechanical properties and sliding properties.
[0091] The formic acid relative viscosity VR of the fiber-reinforced polyamide resin composition is preferably 110 or more, more preferably 130 or more.
[0092] The formic acid relative viscosity can be measured by the method according to ASTM D789 shown in the examples. More specifically, the formic acid relative viscosity VR is measured at 25° C. using a solution obtained by dissolving the fiber-reinforced polyamide resin composition in 90% by mass formic acid (10% by mass water) at a ratio of 8.4% by mass of the soluble components in the fiber-reinforced polyamide resin composition.
[0093] The fiber-reinforced polyamide resin composition of the present embodiment is characterized in that the insoluble components when the fiber-reinforced polyamide resin composition is dissolved in formic acid are 105 mass % or more relative to the ash content of the fiber-reinforced polyamide resin composition. In the present application specification, the ash content of the fiber-reinforced polyamide resin composition can be regarded as the input amount of glass fiber, for example, calculated according to the ash content rate specified in ISO3451-4.
[0094] When the fiber-reinforced polyamide resin composition is dissolved in formic acid, the insoluble matter relative to the ash content (the amount of glass fiber charged) of the fiber-reinforced polyamide resin composition is 105 mass % or more, thereby obtaining a fiber-reinforced polyamide resin molded body having excellent mechanical properties and sliding properties.
[0095] Specifically, the formic acid insoluble content of the fiber-reinforced polyamide resin composition relative to the ash content (the amount of glass fiber input) can be measured by the following method: the fiber-reinforced polyamide resin composition is added to 90% by mass formic acid (10% by mass water), and the solution is dissolved while stirring for one day and night to obtain a solution, and the obtained solution is filtered using a membrane filter with a pore size of 0.65 μm to separate the formic acid insoluble content remaining on the filter paper, and the residual solvent is removed from the separated formic acid insoluble content by air drying for one day and night, and the mass of the obtained dry body is measured, thereby obtaining the formic acid insoluble content by the following formula.
[0096] Formic acid insoluble matter (mass %) = dry mass (g) / fiber-reinforced polyamide resin composition dissolved in formic acid (g) × 100
[0097] The ash content in the sample is measured in advance, for example, based on the provisions of ISO 3451-4, and the amount of formic acid insoluble components relative to the ash content (the amount of glass fiber charged) is calculated by the following formula.
[0098] Formic acid insoluble matter (mass %) relative to ash content = formic acid insoluble matter (mass %) / ash content (mass %) × 100
[0099] Since the fiber-reinforced polyamide resin composition of the present embodiment satisfies the specific composition, sufficient mechanical properties can be imparted to the obtained molded product, the variation in physical properties can be reduced, and sliding properties can be imparted.
[0100] Hereinafter, each component of the fiber-reinforced polyamide resin composition according to the present embodiment will be described in detail.
[0101] ≪(A1) Component: Crystalline polyamide≫
[0102] In the present specification, the term "crystalline polyamide" refers to a polyamide having a crystal melting heat of 4 J / g or more when measured at 20°C / min using a differential scanning calorimeter.
[0103] The terminal amino group concentration [NH2] of the crystalline polyamide contained in the fiber-reinforced polyamide resin composition is preferably 1 milliequivalent / kg or more and 100 milliequivalent / kg or less, more preferably 3 milliequivalent / kg or more and 90 milliequivalent / kg or less, and further preferably 5 milliequivalent / kg or more and 80 milliequivalent / kg or less. When the terminal amino group concentration is within the above range, the color tone of the polyamide resin composition is more excellent and the tendency of yellowing caused by deterioration can be further suppressed.
[0104] The terminal amino group concentration can be measured by dissolving a predetermined amount of a polyamide sample in a 90% by volume phenol aqueous solution, titrating with 1 / 50N hydrochloric acid at 25°C, and calculating the concentration.
[0105] The terminal carboxyl group concentration [COOH] of the crystalline polyamide contained in the fiber-reinforced polyamide resin composition is preferably 10 milliequivalents / kg to 150 milliequivalents / kg, more preferably 20 milliequivalents / kg to 140 milliequivalents / kg, and further preferably 30 milliequivalents / kg to 130 milliequivalents / kg. When the terminal carboxyl group concentration is within the above range, the appearance of the molded article of the fiber-reinforced polyamide resin composition tends to be more excellent.
[0106] The terminal carboxyl group concentration can be measured by dissolving a predetermined amount of a polyamide sample in benzyl alcohol at 160° C. and titrating and calculating the concentration using a 1 / 10N potassium hydroxide solution in ethylene glycol and phenolphthalein as an indicator.
[0107] The ratio of the terminal carboxyl group to the terminal amino group (terminal carboxyl group / terminal amino group) of the crystalline polyamide contained in the fiber-reinforced polyamide resin composition is 0.1 or more, preferably 0.5 or more, and more preferably 1 or more.
[0108] The upper limit of the ratio (terminal carboxyl group / terminal amino group) is, for example, 20 or less, 15 or less, or 10 or less.
[0109] The upper limit and lower limit of the ratio (terminal carboxyl group / terminal amino group) can be arbitrarily combined. Examples of the combination are 0.1 to 20, 0.5 to 15, and 1 to 10.
[0110] When the ratio (terminal carboxyl group / terminal amino group) is within the above range, a molded product having more excellent fatigue properties and gear durability can be easily obtained.
[0111] Here, the ratio of the terminal carboxyl group to the terminal amino group refers to a value expressed by dividing the terminal carboxyl group concentration [COOH] by the terminal amino group concentration [NH 2 ].
[0112] Examples of crystalline polyamides include, but are not limited to: (A1-a) polyamides obtained by ring-opening polymerization of lactams, (A1-b) polyamides obtained by self-condensation of ω-aminocarboxylic acids, (A1-c) polyamides obtained by condensation of diamines and dicarboxylic acids, and copolymers thereof. As crystalline polyamides, one type may be used alone, or two or more types may be used in combination.
[0113] Examples of the lactam used for producing the polyamide (A1-a) include pyrrolidone, caprolactam, undecanolactam, and lauryl lactam, but the lactam is not limited thereto.
[0114] Examples of the ω-aminocarboxylic acid used for producing the polyamide (A1-b) include, but are not limited to, ω-amino fatty acids which are ring-opening compounds of the above-mentioned lactams obtained by water.
[0115] In addition, as the above-mentioned lactam or the above-mentioned ω-aminocarboxylic acid, two or more monomers may be used in combination for condensation.
[0116] Examples of the diamine (monomer) used for producing the polyamide (A1-c) include, but are not limited to, linear aliphatic diamines, branched aliphatic diamines, alicyclic diamines, and aromatic diamines.
[0117] Examples of the linear aliphatic diamine include hexamethylenediamine and pentamethylenediamine, but are not limited thereto.
[0118] Examples of the branched aliphatic diamine include 2-methylpentanediamine and 2-ethylhexamethylenediamine, but are not limited thereto.
[0119] Examples of the alicyclic diamine include cyclohexanediamine, cyclopentanediamine, and cyclooctanediamine, but are not limited thereto.
[0120] Examples of the aromatic diamine include p-phenylenediamine and m-phenylenediamine, but are not limited thereto.
[0121] Examples of the dicarboxylic acid (monomer) used for producing the polyamide (A1-c) include, but are not limited to, aliphatic dicarboxylic acids, alicyclic dicarboxylic acids, and aromatic dicarboxylic acids.
[0122] Examples of the aliphatic dicarboxylic acid include adipic acid, pimelic acid, sebacic acid, and the like, but are not limited thereto.
[0123] Examples of the alicyclic dicarboxylic acid include cyclohexanedicarboxylic acid, but are not limited thereto.
[0124] Examples of the aromatic dicarboxylic acid include phthalic acid and isophthalic acid, but are not limited thereto.
[0125] The diamine and dicarboxylic acid as the above-mentioned monomers may be condensed alone or in combination of two or more.
[0126] It should be noted that the crystalline polyamide may further contain units derived from trivalent or higher polycarboxylic acids such as trimellitic acid, trimesic acid, and pyromellitic acid, as required. The trivalent or higher polycarboxylic acids may be used alone or in combination of two or more.
[0127] Specific examples of the crystalline polyamide contained in the fiber-reinforced polyamide resin composition of the present embodiment include polyamide 4 (poly-α-pyrrolidone), polyamide 6 (polycaproamide), polyamide 11 (polyundecanamide), polyamide 12 (polydodecamide), polyamide 46 (polybutylene adipamide), polyamide 56 (polypentamethylene adipamide), polyamide 66 (polyhexamethylene adipamide), polyamide 610 (polyhexamethylene sebacamide), polyamide 612 (polyhexamethylene dodecaneamide), polyamide 6T (polyhexamethylene terephthalamide), polyamide 9T (polynonane terephthalamide), and copolymer polyamides containing these substances as constituent components.
[0128] Among them, as the crystalline polyamide, polyamide 66 (PA66), polyamide 46 (PA46) or polyamide 610 (PA610) is preferred from the viewpoint of sliding properties. In particular, PA66 is the most preferred material because it is excellent in heat resistance, moldability and toughness and is therefore suitable for automobile parts.
[0129] There are no particular restrictions on the polymerization method of polyamide, and examples thereof include: hot melt polycondensation, solid phase polymerization, and solution method. The hot melt polycondensation method is, for example, the following method: a defoaming agent is added to hexamethylenediamine, which is a raw material of polyamide 66, as required, and the mixture is heated and concentrated at a temperature of 40°C to 300°C, and the generated water vapor pressure is maintained at a pressure between normal pressure and 20 atmospheres, and finally the pressure is removed, and polycondensation is carried out at normal pressure or reduced pressure. In addition, the solid phase polymerization method is a method of polymerizing at a temperature below the melting point of a diamine or a solid salt of a dicarboxylic acid salt or a polycondensation product. In addition, the solution method is a method of polycondensing a dicarboxylic acid halide component and a diamine component in a solution. These methods can be combined as needed. In addition, as a polymerization method, it can be intermittent or continuous. In addition, there is no particular restriction on the polymerization device, and for example, an autoclave reactor, a drum reactor, an extruder reactor such as a kneader, etc. can be used.
[0130] In order to obtain a polyamide having a predetermined formic acid relative viscosity VR, for example, a general method such as a method of adjusting the polymerization time by the above-mentioned hot melt polycondensation method or a method of performing solid phase polymerization at a temperature below the melting point of the polycondensation product can be used without particular limitation.
[0131] ≪(B1) Ingredients: Glass fiber≫
[0132] The fiber-reinforced polyamide resin composition of the present embodiment contains glass fibers (B1).
[0133] The ratio of glass fibers having a fiber length of 250 μm or less in the glass fibers (B1) contained in the polyamide resin composition is 55% or less on a number basis. The glass fibers (B1) having a fiber length of 250 μm or less may be referred to as “short GF”.
[0134] The number average fiber length of the glass fiber (B1) contained in the polyamide resin composition is preferably 300 μm or more, more preferably 350 μm or more.
[0135] The ratio of short GF in all glass fibers (B1) contained in the polyamide resin composition and the number average fiber length of the glass fibers (B1) are specifically measured by the following method. They are obtained by burning or dissolving only the polyamide in the polyamide composition to remove it, then observing it with an optical microscope, measuring the lengths of 400 reinforcing fibers selected at random with an image analyzer, and calculating the ratio of glass fibers of 250 μm or less and the number average fiber length.
[0136] The ratio of the short GF in all the glass fibers contained in the polyamide resin composition is preferably 55% or less, more preferably 50% or less, and further preferably 45% or less.
[0137] The glass fiber preferably has at least a portion of its surface covered with a surface treatment agent. The fiber-reinforced polyamide resin composition includes the glass fiber having at least a portion of its surface covered with a surface treatment agent, so that the glass fiber in the fiber-reinforced polyamide resin composition has excellent fibrillation properties and excellent processability.
[0138] The average fiber diameter of the glass fiber is not particularly limited, but is preferably 4 μm to 30 μm, more preferably 5 μm to 15 μm, more preferably 5 μm to 9 μm, and particularly preferably 5 μm to 8 μm. Here, the average fiber diameter is a number-based value obtained by observation under an electron microscope or the like, and when the average fiber diameter is within the above range, there is a tendency to achieve a polyamide resin composition with better mechanical strength, rigidity, and moldability, and to reduce the variation in mechanical properties.
[0139] As for the glass fiber, commercially available glass fibers available in the form of, for example, chopped glass fibers, glass fiber rovings, milled glass fibers, etc., can be used.
[0140] The surface treatment agent for glass fiber may also contain a sizing agent, without particular limitation, and examples thereof include: polyurethane resin, polycarbodiimide compound, acrylic acid homopolymer, copolymer of acrylic acid and copolymerizable monomer, salt of homopolymer (acrylic acid homopolymer) or copolymer (copolymer of acrylic acid and copolymerizable monomer) and amine, epoxy resin, and copolymer of unsaturated vinyl monomer containing carboxylic anhydride and unsaturated vinyl monomer, etc. These substances may be used alone or in combination of two or more.
[0141] The polyurethane resin is not particularly limited as long as it is a polyurethane resin generally used as a surface treatment agent or sizing agent for glass fibers. For example, a polyurethane resin synthesized from isocyanates such as meta-xylylene diisocyanate (XDI), 4,4'-methylenebis(cyclohexyl isocyanate) (HMDI), and isophorone diisocyanate (IPDI) and polyester diols or polyether diols can be appropriately used.
[0142] The polycarbodiimide compound is not particularly limited, and examples thereof include polycarbodiimide compounds obtained by condensing a compound containing one or more carbodiimide groups (—N═C═N—).
[0143] The weight average molecular weight of the acrylic acid homopolymer is preferably 1,000 to 90,000, more preferably 1,000 to 50,000, and even more preferably 1,000 to 25,000. The weight average molecular weight in the present specification can be determined by measurement using GPC (gel permeation chromatography).
[0144] There are no particular restrictions on the copolymerizable monomers constituting the copolymer of acrylic acid and the copolymerizable monomers, and examples thereof include: monomers having hydroxyl groups and / or carboxyl groups, and ester monomers. There are no particular restrictions on such copolymerizable monomers, and examples thereof include: one or more selected from the group consisting of acrylic acid, maleic acid, methacrylic acid, vinyl acetate, crotonic acid, isocrotonic acid, fumaric acid, itaconic acid, citraconic acid, mesaconic acid, and ester compounds thereof (excluding the case of only acrylic acid). Among the above monomers, it is preferred to have one or more ester monomers.
[0145] The amine that forms a salt with the acrylic acid homopolymer or copolymer is not particularly limited and may be a primary amine, a secondary amine or a tertiary amine. Specific examples thereof include triethylamine, triethanolamine and glycine.
[0146] From the viewpoint of improving the stability of a mixed solution with other chemical agents (such as a silane coupling agent) and reducing amine odor, the degree of neutralization is preferably 20% to 90%, more preferably 30% to 80%, and even more preferably 40% to 60%.
[0147] The weight average molecular weight of the acrylic acid homopolymer or copolymer forming the salt is not particularly limited, but is preferably 3,000 to 50,000. When the weight average molecular weight is 3,000 or more, the bundling property of the glass fiber tends to be further improved. When the weight average molecular weight is 50,000 or less, the mechanical properties of the obtained molded body tend to be further improved.
[0148] As the epoxy resin, there is no particular limitation, for example, a compound having at least two glycidyl groups is preferably used, wherein an epoxy resin obtained by reacting bisphenol with epihalohydrin is suitable. It should be noted that, when considering the bundling of glass fibers, the epoxy equivalent of the epoxy resin is preferably 180 g / equivalent or more, more preferably 450 g / equivalent to 1900 g / equivalent.
[0149] In the glass fiber reinforced polyamide resin composition of this embodiment, as the surface treatment agent or sizing agent of the glass fiber, a copolymer of a carboxylic anhydride-containing unsaturated vinyl monomer and an unsaturated vinyl monomer is preferably included. By including such a copolymer, the mechanical properties of the obtained molded body tend to be more excellent.
[0150] The carboxylic anhydride-containing unsaturated vinyl monomer is not particularly limited, and examples thereof include maleic anhydride, itaconic anhydride, and citraconic anhydride. Among them, maleic anhydride is preferred.
[0151] On the other hand, the unsaturated vinyl monomer is not particularly limited, and examples thereof include styrene, α-methylstyrene, ethylene, propylene, butadiene, isoprene, chloroprene, 2,3-dichloroprene, 1,3-pentadiene, cyclooctadiene, methyl methacrylate, methyl acrylate, ethyl acrylate, and ethyl methacrylate. Among them, ethylene, styrene, and butadiene are preferred.
[0152] Among the combinations of the carboxylic anhydride-containing unsaturated vinyl monomer and the unsaturated vinyl monomer, copolymers of maleic anhydride and butadiene, copolymers of maleic anhydride and ethylene, copolymers of maleic anhydride and styrene, and mixtures thereof are more preferred.
[0153] The weight average molecular weight of the copolymer containing the carboxylic anhydride-containing unsaturated vinyl monomer and the unsaturated vinyl monomer is preferably 2,000 or more, more preferably 2,000 to 1,000,000, and even more preferably 5,000 to 500,000. When the weight average molecular weight is within the above range, the fluidity of the glass fiber reinforced polyamide resin composition tends to be further improved.
[0154] As a surface treatment agent for glass fiber, it is also suitable to use a silane coupling agent. As a silane coupling agent, there is no particular limitation, for example, aminosilanes such as γ-aminopropyl triethoxysilane, γ-aminopropyl trimethoxysilane, N-β-(aminoethyl)-γ-aminopropyl methyl dimethoxysilane; mercaptosilanes such as γ-mercaptopropyl trimethoxysilane, γ-mercaptopropyl triethoxysilane; epoxysilanes; vinylsilanes. Among them, preferably one or more selected from the above-mentioned components, more preferably aminosilanes.
[0155] When preparing the surface treatment agent for glass fiber, it is appropriate to use a lubricant. There is no particular limitation on the lubricant, and for example, any common liquid or solid lubricant material suitable for the purpose can be used. There is no particular limitation on such a lubricant, and for example, animal, plant or mineral waxes such as carnauba wax and lanolin wax; surfactants such as fatty acid amides, fatty acid esters or fatty acid ethers, or aromatic esters or aromatic ethers can be cited.
[0156] (Method of covering the surface of glass fiber with a surface treatment agent)
[0157] In the present embodiment, the glass fiber is preferably a glass fiber whose surface is at least partially covered by a surface treatment agent. There is no particular limitation on the method for covering the surface treatment agent. For example, in a known manufacturing process of the glass fiber, the surface treatment agent can be applied to the glass fiber using a known method such as a roller coater to manufacture the glass fiber precursor, and the manufactured glass fiber precursor is dried to be continuously reacted to obtain the glass fiber precursor.
[0158] It should be noted that there is no particular restriction on the state of the glass fiber, for example, the glass fiber precursor can be used directly in the form of roving, or can be used in the form of chopped glass precursor after further cutting. It should be noted that the precursor can be dried after the cutting process, or the precursor can be dried and then cut.
[0159] The amount of the surface treatment agent for the glass fiber is preferably 0.1 to 1.0 parts by mass, more preferably 0.2 to 1.0 parts by mass, and most preferably 0.2 to 0.6 parts by mass, relative to 100 parts by mass of glass fiber. By making the amount of the surface treatment agent for the glass fiber more than 0.1 parts by mass relative to 100 parts by mass of glass fiber, the coating of the surface treatment agent for the glass fiber is tended to be further maintained. On the other hand, by making the amount of the surface treatment agent for the glass fiber less than 1.0 parts by mass relative to 100 parts by mass of glass fiber, the thermal stability of the fiber-reinforced polyamide resin composition tends to be further improved.
[0160] The polyamide resin composition of the present embodiment preferably contains 1 to 100 parts by mass, more preferably 15 to 50 parts by mass, of the glass fiber (B1) per 100 parts by mass of the crystalline polyamide (A1).
[0161] ≪(C1) Component: Copper compound≫
[0162] It is preferred to add a copper compound to the polyamide resin composition. The copper compound is sometimes recorded as "(C1) component". As the (C1) component, for example, there can be listed: copper halides, copper acetate, copper propionate, copper benzoate, copper adipate, copper terephthalate, copper isophthalate, copper salicylate, copper nicotinate, copper stearate, etc.; copper complex salts obtained by coordination with chelating agents such as ethylenediamine and ethylenediaminetetraacetic acid, etc., but are not limited thereto. These copper compounds can be used alone or in combination of two or more. Among them, copper halides are preferred. From the viewpoint of suppressing the reduction of molecular weight during melt mixing and / or heat aging resistance, cuprous iodide, cuprous bromide, cupric bromide, cuprous chloride, and cupric acetate are further preferred, and cuprous iodide is more preferred.
[0163] ≪(D1) Component: Either or both of halides of alkali metals and alkaline earth metals≫
[0164] It is preferred to add one or both of halides of alkali metals and alkaline earth metals to the polyamide resin composition. One or both of halides of alkali metals and alkaline earth metals may be described as "component (D1)".
[0165] Examples of the component (D1) include, but are not limited to, potassium iodide, potassium bromide, potassium chloride, sodium iodide, sodium chloride, and mixtures thereof. These may be used alone or in combination of two or more.
[0166] As the component (D1), only an alkali metal halide may be used, only an alkaline earth metal halide may be used, or both an alkali metal halide and an alkaline earth metal halide may be used.
[0167] Among them, from the viewpoint of improving heat aging resistance and suppressing metal corrosion, potassium iodide and / or potassium bromide are preferred, and potassium iodide is more preferred.
[0168] The combined use of the components (C1) and (D1) not only provides a better thermal stability effect, but is also more preferred from the viewpoint of suppressing the variation of mechanical properties and improving wear characteristics. The components (C1) and (D1) are preferably contained in the polyamide resin composition in a ratio of 3 / 1 to 50 / 1 in terms of the molar ratio of the halogen content to the copper content (halogen / copper) when used in combination.
[0169] The molar ratio of the halogen content to the copper content (halogen / copper) is more preferably 4 / 1 to 40 / 1, and further preferably 5 / 1 to 30 / 1. It should be noted that the "halogen" referred to herein refers to "halogen elements" such as Br and I. Furthermore, when a copper halide is used as the (C1) component, it refers to the total of the halogen derived from the copper halide and the halogen derived from the (D1) component.
[0170] When the molar ratio of the halogen content to the copper content is within the above range, it is preferred from the viewpoints of suppressing copper precipitation and metal corrosion, suppressing fluctuations in mechanical strength, and improving wear characteristics.
[0171] ≪Heat Stabilizer≫
[0172] It is preferred to add a heat stabilizer to the polyamide resin composition. As the heat stabilizer, there is no particular limitation, and examples thereof include: phenol stabilizers such as hindered phenol compounds, phosphite stabilizers, hindered amine stabilizers, triazine stabilizers, and sulfur-containing stabilizers. The above heat stabilizers can be used alone or in combination of two or more. When a heat stabilizer is contained, there is a tendency to further suppress deterioration caused by heat.
[0173] In the present embodiment, the content of the heat stabilizer is not particularly limited, but from the viewpoint of effectively suppressing degradation caused by heat, preventing coloration, maintaining mechanical properties, etc., the content of the heat stabilizer is preferably 0.005 to 5 parts by mass, more preferably 0.015 to 2 parts by mass, or 0.03 to 0.1 parts by mass, relative to 100 parts by mass of the polyamide resin.
[0174] The phenolic stabilizer is a molecule containing a phenol group, and is not particularly limited, and examples thereof include Irganox (registered trademark) 1098 (manufactured by BASF Corporation).
[0175] The phosphite stabilizer is a molecule containing phosphorus element, and is not particularly limited. Examples thereof include PEP (registered trademark) 36 (manufactured by ADEKA Corporation).
[0176] ≪Other additives≫
[0177] Other additives can be added to the polyamide resin composition as needed within the scope of not damaging the purpose of the present embodiment. As the above-mentioned other additives, there are no particular restrictions, for example, inorganic fillers, antioxidants, ultraviolet absorbers, light degradation prevention agents, plasticizers, lubricants, mold release agents, nucleating agents, flame retardants, colorants other than glass fiber can be added, and other thermoplastic resins can also be mixed. Here, since the properties of the above-mentioned additives are very different, the appropriate content of each component that hardly damages the effect of the present embodiment is various and can be appropriately set respectively.
[0178] <Method for producing fiber-reinforced polyamide resin composition>
[0179] The method for producing the fiber-reinforced polyamide resin composition of the present embodiment is not particularly limited, and the composition can be produced by mixing and kneading (A1) crystalline polyamide and (B1) glass fiber and other components blended as required in any order.
[0180] For fiber reinforced polyamide resin composition, it is preferred to use a method for melt mixing using various extruders commonly used such as single screw or twin screw extruders. From the perspectives of productivity, versatility, etc., it is particularly preferred to use a method using a twin screw extruder. Specifically, when using glass chopped strands as (B1) glass fiber, it is preferred to use the following method: using a twin screw extruder with an upstream supply port and a downstream supply port, supplying glass chopped strands from the upstream supply port and melt mixing. When using a high molecular weight polyamide, sometimes due to the molecular weight reduction of the melt mixing using a twin screw extruder, it is preferred to use the following method: melt mixing of low molecular weight polyamide and (B1) glass fiber in advance, then solid phase polymerization is carried out below the melting point, thus obtaining a high molecular weight fiber reinforced polyamide resin composition. In addition, when using glass fiber roving, it is also possible to utilize known methods to compound.
[0181] <Molded article obtained using the fiber-reinforced polyamide resin composition>
[0182] The molded product of the second embodiment of the present invention is a molded product comprising the fiber-reinforced polyamide resin composition of the first embodiment. For example, the fiber-reinforced polyamide resin composition of the embodiment can be injection-molded to produce molded products of various parts, but there are no particular limitations.
[0183] Furthermore, the molded body in the present embodiment is not particularly limited, and can be applied to various parts such as automobiles, machinery industry, electrical / electronics, industrial materials, industrial materials, daily / household products, etc. As such, the molded body in the present embodiment can impart sufficient mechanical properties and wear characteristics and low property variability to the various parts.
[0184] Examples of the physical property to be subjected to low physical property variability include tensile strength, etc. Examples of the amount of variation that indicates variability include relative amounts of variation such as coefficient of variation, and absolute amounts of variation such as standard deviation.
[0185] In this specification, the coefficient of variation CV refers to the percentage of the ratio of the standard deviation σ to the arithmetic mean μ, and is calculated by CV=(σ / μ)×100.
[0186] The coefficient of variation of the tensile strength of the molded product measured in accordance with ISO527 is preferably 1.0 or less.
[0187] The fiber-reinforced polyamide resin composition of the first embodiment of the present invention is particularly suitable for automotive parts, especially sliding members such as automotive gears, worms, and worm wheels, due to its excellent mechanical properties and wear properties and low property variability.
[0188] <Method for producing thermoplastic resin composition>
[0189] The method for producing a thermoplastic resin composition according to the third embodiment of the present invention includes a melt-kneading step and a heating step. The description of the same configuration as that of the first embodiment or the second embodiment may be omitted.
[0190] The melt kneading step is a step of adding 5 parts by mass to 100 parts by mass of a thermoplastic resin having a viscosity number RV of 25 to 70, and melt kneading the glass fiber having a number average fiber diameter of 3 μm to 15 μm, thereby obtaining a melt kneaded product.
[0191] The heating step (hereinafter sometimes referred to as “solid phase polymerization”) is a step of heating the elliptical columnar pellets of the melt-kneaded product at a temperature T represented by the following formula (I) to obtain a thermoplastic resin composition.
[0192] Tm-130℃≤T≤Tm-10℃ (I)
[0193] (Wherein, Tm is the melting point of the thermoplastic resin.)
[0194] In the production method of this embodiment, the melt-kneaded product is an elliptical columnar pellet having an elliptical columnar shape, and the ratio a / b of the major diameter a to the minor diameter b of the cross section of the elliptical columnar pellet is 1.3 to 3.0.
[0195] In the heating step, the elliptical columnar pellets are heated while being stirred.
[0196] In the prior art, in order to obtain a thermoplastic resin composition having a high molecular weight, a thermoplastic resin is generally polymerized to increase the molecular weight, and then glass fibers are added and melt-kneaded.
[0197] In the prior art, a thermoplastic resin is generally polymerized to increase its molecular weight, and then glass fibers are added and melt-kneaded.
[0198] In contrast, in the manufacturing method of the present embodiment, a thermoplastic resin composition of low to medium molecular weight with a specified viscosity number RV is melt-kneaded together with glass fibers, the melt-kneaded product is extruded into a strand, and pellets of a specific shape are obtained by passing through a water cooling bath, etc., so that when the pellets of the specific shape are solid-phase polymerized, high molecular weight components are selectively added, thereby effectively achieving high molecular weight. In addition, the time required for the solid-phase polymerization can be shortened.
[0199] Hereinafter, each step of the production method according to the present embodiment will be described in detail.
[0200] (Melt-kneading process)
[0201] In the melt kneading step in the production method of this embodiment, glass fibers having a number average fiber diameter of 3 μm to 15 μm are added to a thermoplastic resin having a viscosity number RV of 25 to 70 at a specific mixing ratio and melt kneaded to obtain a melt-kneaded product.
[0202] Specifically, the glass fiber may be added in an amount of 5 to 100 parts by mass, preferably 7 to 95 parts by mass, more preferably 10 to 90 parts by mass, relative to 100 parts by mass of the thermoplastic resin. Alternatively, the glass fiber may be added in an amount of 11 to 100 parts by mass, 11 to 34 parts by mass, or 34 to 100 parts by mass relative to 100 parts by mass of the thermoplastic resin.
[0203] When the blending amount of the glass fiber is equal to or greater than the above lower limit, a thermoplastic resin composition having improved rigidity and strength can be obtained. On the other hand, when the blending amount of the glass fiber is equal to or less than the above upper limit, when the obtained thermoplastic resin composition is molded in various applications, the molding processability becomes further improved.
[0204] As a device for melt kneading, a known device can be used. For example, a single screw or twin screw extruder, a Banbury mixer, a mixing roll or other melt kneading machine can be used. Among them, a multi-screw extruder having a devolatilization mechanism (vent) device and a side feeder device is preferred, and a twin screw extruder is more preferred.
[0205] When the thermoplastic resin and the glass fiber are melt-kneaded by the extruder, the molecular weight of the thermoplastic resin can be adjusted by appropriately setting kneading conditions such as the resin temperature, the degree of reduced pressure, and the average residence time during extrusion.
[0206] The resin temperature during melt kneading is preferably set to be above the melting point of the raw thermoplastic resin and below 370°C, more preferably set to be above the melting point of the raw thermoplastic resin + 5°C and below 350°C, further preferably set to be above the melting point of the raw thermoplastic resin + 10°C and below 340°C, particularly preferably set to be above the melting point of the raw thermoplastic resin + 15°C and below 335°C, and most preferably set to be above the melting point of the raw thermoplastic resin + 20°C and below 330°C. By setting the raw material (resin) temperature during melt kneading to be above the melting point of the raw thermoplastic resin, there is a tendency that the raw thermoplastic resin becomes sufficiently melted and the load on the extruder motor can be further reduced. In addition, by setting the resin temperature during melt kneading to be below 370°C, there is a tendency that the decomposition of the raw thermoplastic resin itself can be further suppressed.
[0207] For example, when polyamide 66 having a melting point of 264° C. is used as the thermoplastic resin, the resin temperature during melt kneading is preferably set to 264° C. or higher and 360° C. or lower, more preferably 270° C. or higher and 350° C. or lower, further preferably 275° C. or higher and 340° C. or lower, particularly preferably 280° C. or higher and 335° C. or lower, and most preferably 285° C. or higher and 330° C. or lower. It should be noted that when a polyamide resin other than polyamide 66 is used as the raw material polyamide resin, it can also be appropriately adjusted according to its melting point.
[0208] The resin temperature during the melt kneading can be measured, for example, by bringing a thermometer such as a thermocouple into direct contact with the melt kneaded product discharged from the discharge port (spinneret) of the extruder. The resin temperature during the melt kneading can be adjusted by adjusting the heater temperature of the barrel of the extruder, or by appropriately adjusting the shear calorific value of the resin by changing the rotation speed and discharge amount of the extruder.
[0209] The average residence time during the melt mixing is preferably set to more than 10 seconds and less than 120 seconds, more preferably set to more than 20 seconds and less than 100 seconds, further preferably set to more than 25 seconds and less than 90 seconds, particularly preferably set to more than 30 seconds and less than 80 seconds, most preferably set to more than 35 seconds and less than 70 seconds. By setting the average residence time during the melt mixing to more than 10 seconds, there is a tendency that the melt mixing can be obtained more effectively. In addition, by setting the average residence time during the melt mixing to less than 120 seconds, there is a tendency that the discharge speed (production speed) of extrusion improves to a certain extent. As a result, there is a tendency that the productivity of polyamide resin composition also becomes better.
[0210] It should be noted that the average residence time refers to the residence time when the residence time in the melt-kneading device is constant, and refers to the average value of the shortest residence time and the longest residence time when the residence time is uneven. The colorant masterbatch in the melt-kneading, the resin used in the melt-kneading process with a color different from the raw material polyamide resin, etc., which can be distinguished from the raw material polyamide resin used in the melt-kneading process (hereinafter referred to as "component X"), are added to the melt-kneading device, and the discharge start time and discharge end time under the most concentrated state of component X are measured, and the discharge start time and discharge end time are averaged, thereby the average residence time can be determined. It should be noted that the above-mentioned average residence time can be appropriately adjusted by the discharge amount (discharge speed) and rotation speed of the extruder.
[0211] The melt-kneaded product (resin composition) obtained in the melt-kneading is subjected to a cooling process to form an elliptical column-shaped pellet having an elliptical column shape. The shape of the elliptical column-shaped pellet can be obtained by adjusting the time for cooling the strands using a water cooling bath or the like. For example, the strands are preferably cooled with a water immersion length of 5 cm to 60 cm, more preferably about 10 cm to about 45 cm, and further preferably about 10 cm to about 30 cm, and cut using a strand cutter.
[0212] In the manufacturing method of the present embodiment, the cross section of the elliptical cylindrical pellets has a specific flat cross section. Specifically, in the cross section of the elliptical cylindrical pellets, the ratio of the major diameter a to the minor diameter b of the cross section (a / b) needs to be 1.3 to 3.0, preferably 1.35 to 2.95, and more preferably 1.4 to 2.9. By having a ratio (a / b) of the major diameter a to the minor diameter b of the cross section of 1.3 or more, high molecular weight can be effectively achieved. By having a ratio (a / b) of the major diameter a to the minor diameter b of the cross section of 3.0 or less, the breakage and cutting of the pellets caused by solid phase polymerization can be suppressed. It should be noted that the cross section of the elliptical cylindrical pellets is a cross section orthogonal to the extension direction (length direction) of the elliptical column of the pellets, and the major diameter and minor diameter of the ellipse are equivalent to the major diameter a and minor diameter b of the above-mentioned cross section. Specifically, the major and minor diameters of the cross sections of 100 pellets were measured with an electronic caliper, the number average major diameter a and the number average minor diameter b were calculated, and the ratio a / b of the major diameter a to the minor diameter b of the pellet cross section was calculated.
[0213] The length of the elliptical columnar pellet is preferably 1.5 mm to 5.0 mm, more preferably 2.0 mm to 4.5 mm, and particularly preferably 2.5 mm to 4.0 mm. When the length of the elliptical columnar pellet is within this range, the pellet is easy to handle.
[0214] The materials used in the melt-kneading step will be described in detail below.
[0215] Thermoplastic resin
[0216] As the thermoplastic resin, the viscosity number RV is 25 or more and 70 or less, preferably the viscosity number RV is 27 or more and 65 or less, more preferably the viscosity number RV is 30 or more and 60 or less, and further preferably the viscosity number RV is 45 or more and 60 or less. When the viscosity number RV is within the above range, the polymerization degree of the thermoplastic resin is within a suitable range, so that the glass fiber and the thermoplastic resin can be kneaded in a state where a large number of polyamide terminal groups are present, and the adhesion at the interface between the glass fiber and the thermoplastic resin can be improved. The viscosity number RV is expressed as a value measured using 90% formic acid at 25° C. as specified in ASTM D789.
[0217] In addition, various thermoplastic resins can be used as the thermoplastic resin, preferably polyamide or polyester, more preferably polyamide. This is because it can more significantly obtain the effect of obtaining a composition with a higher molecular weight under the same solid phase polymerization time and can shorten the time required for solid phase polymerization.
[0218] Examples of the polyamide include polycaproamide (nylon 6), polyhexamethylene adipamide (nylon 66), polybutylene adipamide (nylon 46), polybutylene sebacate (nylon 410), polypentamethylene adipamide (nylon 56), polypentamethylene sebacate (nylon 510), polyhexamethylene sebacate (nylon 610), polyhexamethylene dodecanoyl (nylon 612), polydecanediamide (nylon 106), polydecanediamide (nylon 101 0), polydecanediamide (nylon 1012), polyundecanamide (nylon 11), polydodecanamide (nylon 12), polycaproamide / polyhexamethylene adipamide copolymer (nylon 6 / 66), polycaproamide / polyhexamethylene terephthalamide copolymer (nylon 6 / 6T), polyhexamethylene adipamide / polyhexamethylene terephthalamide copolymer (nylon 66 / 6T), polyhexamethylene adipamide / polyhexamethylene terephthalamide copolymer (nylon 66 / 6I), poly Hexamethylenediamine / polyhexamethyleneisophthalamide copolymer (nylon 6T / 6I), polyhexamethyleneterephthalamide / polyundecanamide copolymer (nylon 6T / 11), polyhexamethyleneterephthalamide / polydodecanamide copolymer (nylon 6T / 12), polyhexamethyleneadipamide / polyhexamethyleneterephthalamide / polyhexamethyleneisophthalamide copolymer (nylon 66 / 6T / 6I), polyphenylene adipamide (nylon XD6), polyphenylene sebacate (nylon XD1 0), polyhexamethylene terephthalamide / polypentamethylene terephthalamide copolymer (nylon 6T / 5T), polyhexamethylene terephthalamide / poly 2-methylpentamethylene terephthalamide copolymer (nylon 6T / M5T), polypentamethylene terephthalamide / polydecamethylene terephthalamide copolymer (nylon 5T / 10T), polynonane terephthalamide (nylon 9T), polydecamethylene terephthalamide (nylon 10T), polydodecane terephthalamide (nylon 12T), etc. It should be noted that " / " means copolymers. These polyamides can be used alone or in combination of two or more.
[0219] Among them, as the polyamide, it is preferred to use one selected from the group consisting of polyamide 6, polyamide 66, polyamide 46, polyamide 610 and polyamide 612, and it is particularly preferred to use polyamide 66. Polyamide 66 itself is a commonly known polyamide resin, which is usually produced by polycondensation of hexamethylenediamine and adipic acid. Alternatively, polyamide 66 can be a copolymer containing less than 30% by mass of at least one or more monomer units selected from the group consisting of lactams, aminocarboxylic acids, and combinations of other diamines and dicarboxylic acids relative to the total mass of all monomer units.
[0220] In addition, these polyamides can use commercially available polyamides or can be manufactured using known methods. As the manufacturing method of the polyamide, specifically, for example, the method described in the first embodiment such as the method of ring-opening polymerization of lactam, the method of self-condensation of ω-aminocarboxylic acid, the method of condensing diamine and dicarboxylic acid can be cited, without particular limitation.
[0221] In addition, the value [NH2] / [COOH] obtained by dividing the amount of amino terminal groups of the polyamide by the amount of carboxyl terminal groups is preferably 0.5 or more and 0.9 or less, and more preferably 0.5 or more and less than 0.6. When [NH2] / [COOH] is within the above range, the interaction between the surface of the glass fiber and the polyamide terminal is more fully increased during melt kneading, and the physical properties of the obtained composition are fully improved. The amount of amino terminal groups and the amount of carboxyl terminal groups can be, for example, 1 H-NMR determination.
[0222] The polyester refers to a condensation product of a polycarboxylic acid (dicarboxylic acid) and a polyol (diol). Examples of the polycarboxylic acid include terephthalic acid, 2,6-naphthalene dicarboxylic acid, and the like. Examples of the polyol include ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,4-cyclohexanedimethanol, and the like. These components may be used alone or in combination of two or more. Specifically, for example, polyesters include polyethylene terephthalate, polypropylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and polybutylene naphthalate.
[0223] Fiberglass
[0224] As for the glass fibers, it is preferred to use glass fibers bundled with a known sizing agent (binder) mainly composed of acrylic resin, epoxy resin, or polyurethane resin, and it is more preferred to use glass fibers bundled with a sizing agent mainly composed of acrylic resin or epoxy resin.
[0225] In order to further improve the mechanical properties of the obtained molded product, it is preferred to use glass fibers pretreated with a coupling agent such as an isocyanate compound, an organic silane compound, an organic titanate compound, an organic borane compound or an epoxy compound.
[0226] The average fiber length of the glass fiber in the melt-kneaded product is preferably 100 μm or more and 1000 μm or less. When the average fiber length of the glass fiber is 100 μm or more, the reinforcing effect can be more reliably and fully exerted, and the impact strength and tensile strength of the obtained thermoplastic resin composition can be further improved. On the other hand, when the average fiber length of the glass fiber is 1000 μm or less, it is possible to more effectively suppress the glass fiber from coming out of the pellets when the obtained melt-kneaded product is made into pellets, thereby reducing the bulk density of the pellets.
[0227] It should be noted that the average fiber length of the glass fiber can be measured, for example, using the following method. First, arbitrarily select more than 100 glass fibers and measure the total mass of the glass fibers. Then, by observing the glass fibers using an optical microscope, a scanning electron microscope, etc., the fiber length of each glass fiber is measured, and the value obtained by dividing the total value of the fiber length of each glass fiber by the total mass of the glass fiber can be obtained as the weight-average fiber length.
[0228] The average fiber diameter of the glass fiber is 3 μm or more and 15 μm or less, preferably 4 μm or more and 13 μm or less, and more preferably 5 μm or more and 10 μm or more. That is, the glass fiber as a raw material is preferably in a very thin shape. The average fiber diameter of the glass fiber is 3 μm or more, and the strength of the glass fiber is more fully high, so the reinforcing effect is more fully exerted. The average fiber diameter of the glass fiber is 15 μm or less, and the surface area of the glass fiber is more fully large, and the effect of further strengthening the closeness at the interface between the glass fiber and the resin is fully exerted.
[0229] It should be noted that the average fiber diameter of the glass fiber can be measured using the following method, for example. First, 100 glass fibers are selected at random. Then, the fiber diameter of each glass fiber is measured by observing the glass fiber using an optical microscope, a scanning electron microscope, etc. The total value of the fiber diameter of each glass fiber divided by 100 can be obtained as the number average fiber diameter.
[0230] Copper compounds
[0231] In the melt-kneading step, a copper compound may be blended in addition to the thermoplastic resin and glass fiber.
[0232] As the copper compound, for example, there can be listed: inorganic acid copper salts such as cuprous chloride, cupric chloride, cuprous bromide, cupric bromide, cuprous iodide (copper iodide (I)), copper sulfate, copper phosphate, copper borate, and copper nitrate; organic acid copper salts such as copper acetate, copper propionate, copper benzoate, copper adipate, copper terephthalate, copper isophthalate, and copper stearate. Alternatively, a copper complex salt coordinated with a chelating agent can be used. Among them, cuprous iodide is preferably used. These copper compounds can be used alone or in combination of two or more.
[0233] The amount of the copper compound is not particularly limited, but is preferably 0.0001 to 1 part by mass, more preferably 0.005 to 0.3 parts by mass, and further preferably 0.02 to 0.1 parts by mass, relative to 100 parts by mass of the thermoplastic resin.
[0234] Metal halides
[0235] In the melt-kneading step, a metal halide may be blended in addition to the above-mentioned thermoplastic resin and glass fiber.
[0236] As the metal halide, potassium halide is preferred. Examples of the potassium halide include potassium iodide, potassium bromide, potassium chloride, etc. Among them, potassium iodide is preferred. These potassium halides may be used alone or in combination of two or more.
[0237] The amount of the metal halide is not particularly limited, but is preferably 0.0001 to 1 part by mass, more preferably 0.005 to 0.8 parts by mass, and even more preferably 0.02 to 0.7 parts by mass, relative to 100 parts by mass of the thermoplastic resin.
[0238] Other resin components
[0239] In the production method of this embodiment, as a raw material resin, in addition to the thermoplastic resin having a viscosity within the above range, other thermoplastic resins having a viscosity outside the above range may be used within the range not impairing the properties of the obtained thermoplastic resin composition.
[0240] As other thermoplastic resins having a viscosity number outside the above range, for example, there can be listed: general-purpose resins such as polyethylene, polypropylene, ethylene-propylene copolymer, polystyrene, ABS resin, AS resin, acrylic resin, etc.; aliphatic polyamide resins such as polyamide 6 and polyamide 11; polycarbonate, polyphenylene ether, polyethylene terephthalate, polybutylene terephthalate, polyphenylene sulfide, etc. These other thermoplastic resins are preferably used after being modified with a modifier such as maleic anhydride or a glycidyl group-containing monomer. Among them, resins without functional groups such as polyethylene, polypropylene or ethylene-propylene copolymer are preferably used after being modified.
[0241] (Heating process)
[0242] The heating step in the production method of the present embodiment is a step of heating the melt-kneaded product at a temperature T represented by the following formula (I) to increase the molecular weight of the thermoplastic resin in the melt-kneaded product by solid phase polymerization to obtain a thermoplastic resin composition.
[0243] Tm-130℃≤T≤Tm-10℃ (I)
[0244] (In formula (I), Tm is the melting point of the thermoplastic resin.)
[0245] The melt-kneaded product obtained in the melt-kneading step may be directly introduced from the extruder into a solid phase polymerization reactor for solid phase polymerization, or may be temporarily packaged and stored in a paper bag or the like and then added to a solid phase polymerization reactor for solid phase polymerization.
[0246] Regarding the heating temperature T in the heating step, by setting it to "melting point of thermoplastic resin - 130°C" or more, the reaction can be accelerated to make it polymerized efficiently, and the target degree of polymerization can be achieved. In addition, by setting the heating temperature T to "melting point of thermoplastic resin - 10°C" or less, not only the thermal decomposition of thermoplastic resin can be further suppressed, the coloring degradation on the polymer surface can be suppressed, but also the fusion of composition pellets can be further suppressed.
[0247] It should be noted that the melting point Tm of the polyamide resin composition can be measured according to JIS-K7121. As a measuring device, for example, Diamond DSC manufactured by PERKIN-ELMER can be used. Specifically, the melting point Tm can be measured using the method described in the examples below.
[0248] In the heating process, the heating time of the melt kneaded product is preferably 30 minutes or more and 15 hours or less within the above temperature range. By making the heating time above the above lower limit, the thermoplastic resin composition can be more effectively made to reach the desired viscosity (degree of polymerization of the thermoplastic resin). By making the heating time below the above upper limit, the fusion of low-order condensation products in solid phase polymerization and the coloring (yellowing) of the composition can be more effectively suppressed.
[0249] It should be noted that the solid phase polymerization reaction can be carried out in any of a continuous mode or an intermittent mode. As a solid phase polymerization reactor, it can be a vertical type or a horizontal type. In order to improve the uniformity of the reaction, the solid phase polymerization reaction is preferably stirred. The polymerization reactor can be a main body rotating type or a stirring type utilizing a stirring blade or the like. Among them, the solid phase polymerization reaction in the heating step is preferably carried out continuously.
[0250] The solid phase polymerization reaction in the heating step may be performed under vacuum or under a gas flow, and is preferably performed under a gas flow of an inert gas such as nitrogen.
[0251] When the solid phase polymerization is carried out under an inert gas flow, it is preferably carried out under an inert gas atmosphere with an oxygen concentration of 5 ppm or less. By setting the oxygen concentration to 5 ppm or less, the oxidative degradation of the obtained thermoplastic resin composition can be more effectively suppressed. Thus, the reaction of molecular chain severance and the decrease in the rate of molecular weight increase (polymerization reaction rate) can be further suppressed, and a thermoplastic resin composition of a specified molecular weight can be obtained. In addition, the decrease in mechanical properties and yellowing of the obtained thermoplastic resin can be more effectively suppressed.
[0252] In addition, when solid phase polymerization is performed under an inert gas flow, it is preferably performed under an inert gas atmosphere with a water concentration of 10 ppm or less. When the water concentration is 10 ppm or less, the hydrolysis reaction of the thermoplastic resin can be more effectively suppressed. Thus, the decrease in the rate of molecular weight increase (polymerization reaction rate) can be further suppressed, and a thermoplastic resin composition with a predetermined molecular weight can be obtained.
[0253] In addition, when the solid-phase polymerization is carried out under an inert gas flow, it is preferred to form a particle layer using molten kneaded material pellets, and the solid-phase polymerization reaction is carried out while supplying the inert gas in an amount of 50 L / hour to 1000 L / hour, preferably 100 L / hour to 900 L / hour, and particularly preferably 200 L / hour to 800 L / hour, relative to 10 kg of the molten kneaded material pellets, at a height of more than 0 times and less than 0.8 times, preferably more than 0 times and less than 0.5 times, the height of the particle layer.
[0254] It should be noted that the height h of the particle layer of the melt-kneaded pellets is defined as follows. The solid phase polymerization reactor is opened, and a considerable amount of particles or pellets of the melt-kneaded product is put into operation at room temperature and atmospheric pressure. Under the condition of passing a prescribed amount of inert gas, the height of the particle layer is measured with the bottom of the reactor having a gas supply port as the reference (h=0), and it is taken as h. In the case where the height surface of the particle layer varies, the highest height and the lowest height can also be measured, and their average value is taken as h.
[0255] <Thermoplastic resin composition>
[0256] The thermoplastic resin composition obtained by the production method of the present embodiment is excellent in mechanical properties, long-term properties, and productivity.
[0257] The viscosity number RV of the thermoplastic resin composition of the present embodiment is preferably 70 to 400, more preferably 80 to 380, further preferably 90 to 350, and further preferably 150 to 200. When the RV is at least the above lower limit, the mechanical properties are further improved, while when the RV is at most the above upper limit, the molding processability is further improved when molding is performed in various applications.
[0258] In addition, the content of the glass fiber in the thermoplastic resin composition of the present embodiment is preferably 5 parts by mass or more and 100 parts by mass or less, and more preferably 10 parts by mass or more and 100 parts by mass or less, relative to 100 parts by mass of the thermoplastic resin. By making the content of the glass fiber 5 parts by mass or more relative to 100 parts by mass of the thermoplastic resin, the rigidity and strength of the thermoplastic resin composition can be further improved. On the other hand, by making the content of the glass fiber 100 parts by mass or less relative to 100 parts by mass of the thermoplastic resin, the molding processability becomes better when the thermoplastic resin composition is molded in various applications.
[0259] In addition, the weight average fiber length of the glass fiber contained in the thermoplastic resin composition of the present embodiment is preferably 100 μm or more and 1000 μm or less. When the average fiber length of the glass fiber is 100 μm or more, the reinforcing effect can be more fully exerted, and the impact strength and tensile strength can be further improved. On the other hand, when the average fiber length of the glass fiber is 1000 μm or less, it is possible to more effectively suppress the glass fiber from bubbling out of the pellets when the thermoplastic resin composition is made into pellets, thereby reducing the bulk density of the pellets.
[0260] The average fiber length of the glass fibers contained in the thermoplastic resin composition can be measured, for example, by the following method.
[0261] First, a thermoplastic resin composition is dissolved using a solvent such as formic acid that can dissolve a thermoplastic resin. Next, arbitrarily select, for example, 100 or more glass fibers from the obtained insoluble components, and measure the total mass of the glass fibers. Next, the fiber length of each glass fiber is measured by observing the glass fibers using an optical microscope, a scanning electron microscope, etc., and the value obtained by dividing the total value of the fiber length of each glass fiber by the total mass of the glass fibers can be obtained as the weight-average fiber length.
[0262] By adopting the method for producing a thermoplastic resin composition according to the present embodiment, molecular weight is promoted, productivity is improved, and the obtained thermoplastic resin composition has excellent mechanical properties and long-term properties, so it can be suitably used in, for example, automobile parts, electronic and electrical parts, industrial machine parts, various gears, etc.
[0263] <Method for producing thermoplastic resin composition>
[0264] The method for producing a thermoplastic resin composition of the fourth embodiment of the present invention includes a melt kneading step and a heating step. The method for producing the present embodiment may be a method consisting of only a melt kneading step and a heating step, or may further include other steps. Regarding the same configuration as the first embodiment, the second embodiment, and the third embodiment, the description thereof is sometimes omitted.
[0265] In the melt-kneading step, 5 parts by mass or more and 100 parts by mass or less of glass fibers having an average fiber diameter of 3 μm or more and 9 μm or less are added to 100 parts by mass of a thermoplastic resin having a viscosity number VN of 80 or more and 200 or less, and melt-kneading is performed to obtain a melt-kneaded product. The melt-kneaded product may be a kneaded product consisting of only the thermoplastic resin and the glass fibers, or may further contain other components.
[0266] In the heating step, the melt-kneaded product obtained in the melt-kneading step is heated at a temperature T represented by the following formula (I) to obtain a thermoplastic resin composition. In this specification, the temperature T and the melting point Tm are expressed in degrees Celsius.
[0267] Tm-130℃≤T≤Tm-10℃ (I)
[0268] (In formula (I), Tm is the melting point of the above thermoplastic resin.)
[0269] In the heating step, 0.05% by mass to 1.0% by mass of water is contained based on 100% by mass of the melt-kneaded product obtained in the melt-kneading step.
[0270] In a conventional method for producing a thermoplastic resin composition, a thermoplastic resin is polymerized to increase its molecular weight, and then a filler such as glass fiber is added and melt-kneaded to obtain a thermoplastic resin composition.
[0271] In contrast, in the manufacture method of the present embodiment, thermoplastic resin and glass fiber with low molecular weight to medium molecular weight are melt-mixed to obtain melt-mixed product. Thus, the closeness at the interface of glass fiber and thermoplastic resin improves. Then, by heating process, the melt-mixed product is solid-phase polymerized and high molecular weighted, thus keeping the state of the closeness at the interface of glass fiber and thermoplastic resin improving, it is possible to obtain the thermoplastic resin composition with excellent vibration fatigue resistance. In addition, by successively implementing melt-mixing process and heating process, keeping the state of the closeness at the interface of glass fiber and thermoplastic resin improving, filler is not easy to fall off during manufacturing.
[0272] Hereinafter, each step of the production method according to the present embodiment will be described in detail.
[0273] [Melt-kneading process]
[0274] In the melt-kneading step, glass fibers having an average fiber diameter of 3 μm to 9 μm are added to a thermoplastic resin having a viscosity number VN of 80 to 200 at a ratio to achieve a specific blending ratio, and melt-kneaded to obtain a melt-kneaded product. Specifically, the glass fibers may be added in an amount of 5 to 100 parts by mass, preferably 10 to 100 parts by mass, more preferably 15 to 100 parts by mass, and further preferably 20 to 90 parts by mass, relative to 100 parts by mass of the thermoplastic resin.
[0275] When the amount of glass fiber blended is equal to or greater than the above lower limit, a thermoplastic resin composition having improved rigidity and strength can be obtained. On the other hand, when the amount of glass fiber blended is equal to or less than the above upper limit, the molding processability becomes further improved when the obtained thermoplastic resin composition is molded in various applications.
[0276] As a device for melt kneading, a known device can be used. For example, a single screw or twin screw extruder, a Banbury mixer, a mixing roll or other melt kneading machine can be used. Among them, a multi-screw extruder having a devolatilization mechanism (vent) device and a side feeder device is preferred, and a twin screw extruder is more preferred.
[0277] When melt kneading is performed using an extruder, the molecular weight of the thermoplastic resin after melt kneading can be adjusted by appropriately setting kneading conditions such as the resin temperature during extrusion, the degree of reduced pressure, and the average residence time.
[0278] The resin temperature during melt kneading is preferably set to a temperature not less than the melting point of the raw thermoplastic resin and not more than 370°C, more preferably not less than the melting point of the raw thermoplastic resin + 5°C and not more than 350°C, further preferably not less than the melting point of the raw thermoplastic resin + 10°C and not more than 340°C, particularly preferably not less than the melting point of the raw thermoplastic resin + 15°C and not more than 335°C, and most preferably not less than the melting point of the raw thermoplastic resin + 20°C and not more than 330°C.
[0279] By setting the resin temperature during melt kneading to be above the above lower limit, the raw material thermoplastic resin is sufficiently melted, and the load on the extruder motor tends to be further reduced. In addition, by setting the resin temperature during melt kneading to be below the above upper limit, the decomposition of the raw material thermoplastic resin itself tends to be further suppressed.
[0280] By appropriately setting the kneading conditions such as the resin temperature, the degree of decompression, and the average residence time during melt kneading (e.g., during extrusion), the weight average molecular weight of the thermoplastic resin after melt kneading can be controlled within the range of low molecular weight to medium molecular weight. Here, the range of low molecular weight to medium molecular weight refers to the range of weight average molecular weight of 10,000 to 70,000, 15,000 to 65,000, and 20,000 to 60,000.
[0281] For example, when polyamide 66 having a melting point of 264°C is used as the raw thermoplastic resin, the resin temperature during melt kneading is preferably set to 264°C to 360°C, more preferably to 270°C to 350°C, further preferably to 275°C to 340°C, particularly preferably to 280°C to 335°C, and most preferably to 285°C to 330°C.
[0282] By setting the resin temperature during melt kneading to be above the lower limit, polyamide 66 is melted more fully, and there is a tendency that the load on the extruder motor can be further reduced. In addition, by setting the resin temperature during melt kneading to be below the upper limit, there is a tendency that the decomposition of polyamide 66 itself can be further suppressed.
[0283] When a polyamide resin other than polyamide 66 is used as the raw material polyamide resin, it can be appropriately adjusted according to its melting point. The above-mentioned resin temperature can be measured, for example, by bringing a thermometer such as a thermocouple into direct contact with the molten kneaded product discharged from the discharge port (spinneret) of the extruder. The resin temperature can be adjusted by adjusting the heater temperature of the barrel of the extruder, by changing the rotation speed of the extruder, and by appropriately adjusting the shear calorific value of the resin.
[0284] The average residence time during melt kneading is preferably 10 seconds to 120 seconds, more preferably 20 seconds to 100 seconds, further preferably 25 seconds to 90 seconds, particularly preferably 30 seconds to 80 seconds, and most preferably 35 seconds to 70 seconds.
[0285] By setting the average residence time during melt kneading to above the above lower limit, there is a tendency that the melt kneaded product can be obtained more effectively. In addition, by setting the average residence time during melt kneading to below the above upper limit, there is a tendency that the discharge speed (production speed) of extrusion is improved to a certain extent. As a result, there is a tendency that the productivity of thermoplastic resin compositions such as polyamide resin compositions also becomes better.
[0286] The average residence time refers to the residence time when the residence time in the melt-kneading device is constant.
[0287] When the residence time is uneven, the average residence time refers to the average of the shortest residence time and the longest residence time.
[0288] The average residence time is measured by the following method.
[0289] Component X is added to a melt-kneading device, and the discharge start time and discharge end time are measured in the most concentrated state of component X. The average residence time can be measured by averaging the measured discharge start time and discharge end time. Component X refers to a component that can be distinguished from the raw material polyamide resin used in the melt-kneading process, such as a colorant masterbatch in melt-kneading, a resin with a different color from the raw material polyamide resin used in the melt-kneading process, and the like.
[0290] The above average residence time can be appropriately adjusted by the discharge volume (discharge rate) and rotation speed of the extruder.
[0291] The melt-kneaded product obtained by melt kneading can be a resin pellet, and can also be provided in various shapes. Preferred pellet shapes include: round, oval, cylindrical, etc., and these shapes vary depending on the cutting method during extrusion processing. Pellets cut by a cutting method called underwater cutting are often round, pellets cut by a cutting method called thermal cutting are often round or oval, and pellets cut by a cutting method called wire cutting are often cylindrical.
[0292] The round pellets may be a perfect sphere, or a shape that is close to a perfect sphere even if it is not a perfect sphere. The preferred size of the round pellets is 8 mm or less in terms of pellet diameter (in the case of a perfect sphere approximation, the maximum diameter), more preferably 0.5 mm or more and 6 mm or less, and even more preferably 1 mm or more and 5 mm or less.
[0293] The elliptical pellets may be ellipsoids, or even if not perfect ellipsoids, they may be approximated to ellipsoids. In the case of elliptical pellets, the preferred size is 8 mm or less, more preferably 0.5 mm or more and 6 mm or less, and further preferably 1 mm or more and 5 mm or less, based on the pellet major radius (in the case of an ellipsoid approximation, the maximum major radius).
[0294] The cylindrical pellets may be cylindrical, or may be close to a cylindrical shape even if not a perfect cylindrical shape. The preferred size of the cylindrical pellets is 1 mm to 3 mm in terms of pellet diameter (in the case of a cylindrical approximation, the maximum diameter), and the preferred length is 2 mm to 10 mm.
[0295] The raw materials used in the melt-kneading step will be described in detail below.
[0296] (Thermoplastic resin)
[0297] As a thermoplastic resin, any thermoplastic resin having a viscosity number VN of 80 or more and 200 or less can be used, preferably a thermoplastic resin having a viscosity number VN of 100 or more and 200 or less, and more preferably a thermoplastic resin having a viscosity number VN of 130 or more and 190 or less. By keeping the viscosity number VN within the above range, the degree of polymerization of the thermoplastic resin within a suitable range, and the closeness at the interface between the glass fiber and the thermoplastic resin can be improved. The viscosity number VN is a value measured according to ISO307 (JIS-K6933). For example, it can be measured using the method shown in the embodiments described later.
[0298] The resin component in the thermoplastic resin composition may be only the above-mentioned thermoplastic resin having a viscosity number VN within the above-mentioned range.
[0299] Specifically, as the thermoplastic resin, polyamide or polyester is preferred, and polyamide is more preferred.
[0300] Examples of the polyamide include polycaproamide (nylon 6), polyhexamethylene adipamide (nylon 66), polybutylene adipamide (nylon 46), polybutylene sebacate (nylon 410), polypentamethylene adipamide (nylon 56), polypentamethylene sebacate (nylon 510), polyhexamethylene sebacate (nylon 610), polyhexamethylene dodecanoylamide (nylon 612), polydecanediamide (nylon 106), and polydecanediamide (nylon 1010). , polydecanediamide (nylon 1012), polyundecanamide (nylon 11), polydodecanamide (nylon 12), polycaproamide / polyhexamethylene adipamide copolymer (nylon 6 / 66), polycaproamide / polyhexamethylene terephthalamide copolymer (nylon 6 / 6T), polyhexamethylene adipamide / polyhexamethylene terephthalamide copolymer (nylon 66 / 6T), polyhexamethylene adipamide / polyhexamethylene terephthalamide copolymer (nylon 66 / 6I), polyterephthalamide Hexamethylenediamine / polyhexamethyleneisophthalamide copolymer (nylon 6T / 6I), polyhexamethyleneterephthalamide / polyundecanamide copolymer (nylon 6T / 11), polyhexamethyleneterephthalamide / polydodecanamide copolymer (nylon 6T / 12), polyhexamethylenediamine / polyhexamethyleneterephthalamide / polyhexamethyleneisophthalamide copolymer (nylon 66 / 6T / 6I), polyphenylene adipamide (nylon XD6), polyphenylene sebacate (nylon XD1 0), polyhexamethylene terephthalamide / polypentamethylene terephthalamide copolymer (nylon 6T / 5T), polyhexamethylene terephthalamide / poly 2-methylpentamethylene terephthalamide copolymer (nylon 6T / M5T), polypentamethylene terephthalamide / polydecamethylene terephthalamide copolymer (nylon 5T / 10T), polynonane terephthalamide (nylon 9T), polydecamethylene terephthalamide (nylon 10T), polydodecane terephthalamide (nylon 12T), etc. It should be noted that " / " means copolymers. These polyamides can be used alone or in combination of two or more.
[0301] Among them, as the polyamide, polyamide 6, polyamide 66 or polyamide 610 is preferred, and polyamide 66 is particularly preferred. Polyamide 66 itself is a generally known polyamide resin, and is generally produced by polycondensation of hexamethylenediamine and adipic acid. Alternatively, polyamide 66 may be a copolymer containing less than 30% by mass of at least one or more monomer units selected from the group consisting of lactams, aminocarboxylic acids, and combinations of other diamines and dicarboxylic acids relative to the total mass of all monomer units.
[0302] In addition, these polyamides can use commercially available polyamides or can be manufactured using known methods. As the manufacturing method of the polyamide, specifically, for example, the method described in the first embodiment such as the method of ring-opening polymerization of lactam, the method of self-condensation of ω-aminocarboxylic acid, the method of condensing diamine and dicarboxylic acid can be cited, without particular limitation.
[0303] The value [COOH] / [NH2] obtained by dividing the amount of amino terminal groups of the polyamide by the amount of carboxyl terminal groups is preferably 0.5 or more and 0.9 or less. When [COOH] / [NH2] is above the above lower limit, solid phase polymerization can be more effectively performed in the heating step described later. When [COOH] / [NH2] is below the above upper limit, the interaction between the surface of the glass fiber and the polyamide terminal is more fully increased, and the physical properties of the obtained composition, especially the vibration fatigue resistance, are fully improved. The amount of amino terminal groups and the amount of carboxyl terminal groups can be, for example, 1 H-NMR determination.
[0304] Polyester refers to a condensation product of a polycarboxylic acid (dicarboxylic acid) and a polyol (diol). Examples of the polycarboxylic acid include terephthalic acid, 2,6-naphthalene dicarboxylic acid, and the like. Examples of the polyol include ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,4-cyclohexanedimethanol, and the like. These components may be used alone or in combination of two or more. Specifically, for example, polyester includes polyethylene terephthalate, polypropylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, and the like.
[0305] (Fiberglass)
[0306] For the glass fiber, it is preferred to use a glass fiber that has been bundled using a known sizing agent (binder) with acrylic resin, epoxy resin or polyurethane resin as the main component, and it is more preferred to use a glass fiber that has been bundled using a sizing agent with acrylic resin or epoxy resin as the main component. In addition, from the perspective of further improving the mechanical properties of the obtained molded product, it is preferred to use a glass fiber that has been pre-treated with a coupling agent such as an isocyanate compound, an organic silane compound, an organic titanate compound, an organic borane compound or an epoxy compound.
[0307] The average fiber length of the glass fiber is preferably 100 μm or more and 1000 μm or less. When the average fiber length is above the lower limit, the reinforcing effect can be more fully exerted, and the impact strength and tensile strength of the obtained thermoplastic resin composition can be further improved. On the other hand, when the obtained thermoplastic resin composition is made into pellets by the average fiber length being below the upper limit, the glass fiber is not easy to emerge from the pellets. As a result, the bulk density of the pellets is less likely to decrease.
[0308] The average fiber length of the glass fibers can be measured, for example, by the following method.
[0309] First, arbitrarily select, for example, more than 100 glass fibers, and measure the total mass of the glass fibers. Next, the fiber length of each glass fiber is measured by observing the glass fibers using an optical microscope, a scanning electron microscope, etc., and the value obtained by dividing the total value of the fiber length of each glass fiber by the total mass of the glass fibers can be obtained as the weight-average fiber length.
[0310] The average fiber diameter of the glass fiber is 3 μm or more and 9 μm or less, preferably 4 μm or more and 8 μm or less, more preferably 5 μm or more and 7 μm or more. By having an average fiber diameter of more than the above lower limit, the strength of the glass fiber is more fully high, so the reinforcing effect is more fully exerted. By having an average fiber diameter of less than the above upper limit, the surface area of the glass fiber is more fully large, fully exerting the effect of further strengthening the closeness at the interface of the glass fiber and the resin.
[0311] The average fiber diameter of the glass fibers can be measured, for example, by the following method.
[0312] First, 100 glass fibers are randomly selected, for example, and then the fiber diameter of each glass fiber is measured by observing the glass fibers using an optical microscope, a scanning electron microscope, etc. The total value of the fiber diameters of the glass fibers is divided by 100 to obtain the value as the number average fiber diameter.
[0313] Commonly used glass fibers are called "E glass" and contain about 7% by mass of boron oxide relative to the total mass of the glass fibers. The glass fibers contained in the thermoplastic resin composition of the present embodiment preferably do not contain substantially boron oxide in its composition. That is, the obtained thermoplastic resin composition preferably does not contain substantially boron oxide. By not containing substantially boron oxide, the physical properties of the composition, especially the vibration fatigue resistance, become better.
[0314] It should be noted that the term "substantially free of boron oxide" as used herein means that boron oxide is completely free of boron oxide or is contained in a very small amount to such an extent that the properties (particularly vibration fatigue resistance) of the obtained thermoplastic resin composition are not impaired. Specifically, the content of boron oxide is preferably less than 5% by mass, more preferably less than 1% by mass, further preferably less than 0.1% by mass, and particularly preferably 0% by mass, relative to the total mass of the thermoplastic resin composition.
[0315] (Copper compounds)
[0316] In the melt kneading step, a copper compound may be blended in addition to the thermoplastic resin and the glass fiber.
[0317] As the copper compound, for example, there can be listed: inorganic acid copper salts such as cuprous chloride, cupric chloride, cuprous bromide, cupric bromide, cuprous iodide (copper iodide (I)), copper sulfate, copper phosphate, copper borate, and copper nitrate; organic acid copper salts such as copper acetate, copper propionate, copper benzoate, copper adipate, copper terephthalate, copper isophthalate, and copper stearate. Alternatively, a copper complex salt coordinated with a chelating agent can be used. Among them, cuprous iodide is preferably used. These copper compounds can be used alone or in combination of two or more.
[0318] The amount of the copper compound is preferably 0.0001 to 1 part by mass, more preferably 0.005 to 0.2 parts by mass, and even more preferably 0.02 to 0.1 parts by mass, relative to 100 parts by mass of the thermoplastic resin.
[0319] (Metal Halide)
[0320] In the melt kneading step, a metal halide may be blended in addition to the thermoplastic resin and the glass fiber.
[0321] As the metal halide, potassium halide is preferred. Examples of the potassium halide include potassium iodide, potassium bromide, potassium chloride, etc. Among them, potassium iodide is preferred. These potassium halides may be used alone or in combination of two or more.
[0322] The amount of the metal halide to be blended is preferably 0.0001 to 1 part by mass, more preferably 0.005 to 0.2 parts by mass, and still more preferably 0.02 to 0.15 parts by mass, relative to 100 parts by mass of the thermoplastic resin.
[0323] (Other resin components)
[0324] In the production method of this embodiment, as a raw material resin, in addition to the thermoplastic resin having a viscosity within the above range, other thermoplastic resins having a viscosity outside the above range may be used within the range not impairing the properties of the obtained thermoplastic resin composition.
[0325] As other thermoplastic resins having a viscosity number outside the above range, for example, there can be listed: general-purpose resins such as polyethylene, polypropylene, ethylene-propylene copolymer, polystyrene, ABS resin, AS resin, acrylic resin, etc.; aliphatic polyamide resins such as polyamide 6 and polyamide 11; polycarbonate, polyphenylene ether, polyethylene terephthalate, polybutylene terephthalate, polyphenylene sulfide, etc. These other thermoplastic resins are preferably used after being modified with a modifier such as maleic anhydride or a glycidyl group-containing monomer. Among them, resins without functional groups such as polyethylene, polypropylene or ethylene-propylene copolymer are preferably used after being modified.
[0326] [Heating process]
[0327] In the heating step, the melt-kneaded product is heated at a temperature T represented by the following formula (I) to increase the molecular weight of the thermoplastic resin in the melt-kneaded product by solid phase polymerization, thereby obtaining a thermoplastic resin composition.
[0328] Tm-130℃≤T≤Tm-10℃ (I)
[0329] (In formula (I), Tm is the melting point of the above thermoplastic resin.)
[0330] The melt-kneaded product obtained in the melt-kneading step may be directly introduced from the extruder into a solid phase polymerization reactor for solid phase polymerization, or may be temporarily packaged and stored in a paper bag or the like and then added to a solid phase polymerization reactor for solid phase polymerization.
[0331] When the temperature T is "melting point of the thermoplastic resin - 130° C." or higher, the reaction can be accelerated to allow efficient polymerization, and a target degree of polymerization can be achieved.
[0332] When the temperature T is "melting point of the thermoplastic resin - 10°C" or lower, the thermoplastic resin is less likely to be thermally decomposed, and coloration degradation on the polymer surface can be suppressed. In addition, fusion of solid prepolymers can be further suppressed.
[0333] The temperature T is preferably Tm-110°C or higher and Tm-30°C or lower.
[0334] The melting point Tm of the thermoplastic resin can be measured in accordance with JIS-K7121. As a measuring device, for example, Diamond DSC manufactured by PERKIN-ELMER can be used. Specifically, the melting point Tm can be measured by the method described in the examples described later.
[0335] In the heating process, the heating time of the melt kneaded product is preferably more than 30 minutes and less than 15 hours within the above temperature range. By making the heating time more than the above lower limit, the thermoplastic resin composition can be more effectively achieved to the desired viscosity (degree of polymerization of the thermoplastic resin). By making the heating time less than the above upper limit, the fusion of low-order condensation products in solid phase polymerization and the coloring (yellowing) of the composition can be more effectively suppressed.
[0336] The solid phase polymerization reaction can be carried out in any of a continuous mode or an intermittent mode. As a solid phase polymerization reactor, it can be a vertical type or a horizontal type. In order to improve the uniformity of the reaction, the solid phase polymerization reaction is preferably stirred. The polymerization reactor can be a main body rotating type or a stirring type using a stirring blade or the like. Among them, the solid phase polymerization reaction in the heating step is preferably carried out continuously.
[0337] In addition, water is contained in the solid phase polymerization reaction in the heating step. The amount of water is 0.05% to 1.0% by mass, preferably 0.06% to 0.9% by mass, more preferably 0.07% to 0.8% by mass, and particularly preferably 0.11% to 0.8% by mass, relative to 100% by mass of the melt-kneaded pellets obtained in the above-mentioned melt-kneading. By containing the above-mentioned amount of water during the solid phase polymerization reaction, the coloring (yellowing) of the composition can be suppressed and the vibration fatigue resistance can be improved.
[0338] The amount of water may be a ratio of water before the start of heating in the heating step.
[0339] Regarding the addition of water in the solid phase polymerization reaction, for example, it can be added after the melt-kneaded product is filled into the solid phase polymerization device. For the purpose of making water uniformly adhere to the melt-kneaded product, it is preferred to add water while stirring the melt-kneaded product. In addition, water can also be added by subjecting the melt-kneaded product to water absorption treatment before implementing the solid phase polymerization reaction.
[0340] The solid phase polymerization reaction in the heating step may be performed under any conditions, either in vacuum or under a gas flow. Among them, it is preferably performed under a gas flow of an inert gas such as nitrogen.
[0341] When solid phase polymerization is carried out under an inert gas flow, it is preferably carried out under an inert gas atmosphere with an oxygen concentration of 5 ppm or less. When the oxygen concentration is below the above upper limit, the obtained thermoplastic resin composition is not prone to oxidative degradation. As a result, the reaction of molecular chain severance is not easy to occur, the rate of molecular weight increase (polymerization reaction rate) is not easy to decrease, and a thermoplastic resin composition of a specified molecular weight is easily obtained. In addition, the reduction of mechanical properties and yellowing of the obtained thermoplastic resin composition can be more effectively suppressed.
[0342] When solid phase polymerization is performed under an inert gas flow, it is preferred that a particle layer is formed from the melt-kneaded product and a solid phase reaction is performed while supplying a predetermined amount of inert gas at a predetermined position at the height of the particle layer.
[0343] Specifically, the particle layer is preferably moved at a height of 0 to 0.8 times, preferably 0 to 0.5 times, the height h of the particle layer at a speed of 0.1 Nm / s with respect to 1 kg of the melt-kneaded product. 3 / hour and above and 10Nm 3 / hour or less, preferably 0.14Nm 3 / hour and above and 10Nm 3 The solid phase polymerization reaction is carried out while supplying an inert gas in an amount of less than 1 / hour.
[0344] It should be noted that the height h of the particle layer is defined as follows.
[0345] Open the solid phase polymerization reactor, put in a considerable amount of molten mixed particles or pellets at room temperature and atmospheric pressure, and measure the height of the particle layer with the bottom of the reactor having a gas supply port as the reference (h=0) while passing a prescribed amount of inert gas. This height is taken as h.
[0346] When the height surface of the particle layer is not constant, the average value of the highest height and the lowest height is taken as h.
[0347] From the viewpoint of further improving the vibration fatigue resistance and further suppressing the coloration, the ratio of the viscosity number VN of the thermoplastic resin composition after the heating step to the viscosity number VN of the thermoplastic resin added in the melt-kneading step (viscosity number VN of the thermoplastic resin composition after the heating step / viscosity number VN of the thermoplastic resin added in the melt-kneading step) is preferably 1.0 to 5.0, more preferably 1.1 to 4.0, and even more preferably 1.2 to 3.0.
[0348] <Thermoplastic resin composition>
[0349] The viscosity number VN of the thermoplastic resin composition obtained by the production method of the present embodiment is preferably 200 to 350, more preferably 210 to 330, and even more preferably 220 to 300. When VN is at least the above lower limit, wear resistance is further improved, while when VN is at most the above upper limit, molding processability is further improved when molding is performed in various applications.
[0350] The content of the glass fiber in the thermoplastic resin composition is preferably 5 parts by mass or more and 100 parts by mass or less, and more preferably 15 parts by mass or more and 100 parts by mass or less, relative to 100 parts by mass of the thermoplastic resin. When the content of the glass fiber is above the above lower limit, the rigidity and strength of the thermoplastic resin composition can be further improved. On the other hand, when the content of the glass fiber is below the above upper limit, the molding processability becomes better when the thermoplastic resin composition is molded in various applications.
[0351] The average fiber length of the glass fiber contained in the thermoplastic resin composition is preferably 100 μm or more and 1000 μm or less, more preferably 200 μm or more and 600 μm or less, and more preferably 300 μm or more and 500 μm or less. When the average fiber length is above the lower limit, the reinforcing effect can be more fully exerted, and the impact strength and tensile strength can be further improved. On the other hand, when the thermoplastic resin composition is made into pellets, the glass fiber is not easy to emerge from the pellets. As a result, the bulk density of the pellets is not easy to decrease.
[0352] The average fiber length of the glass fibers contained in the thermoplastic resin composition can be measured, for example, by the following method.
[0353] First, a thermoplastic resin composition is dissolved in a solvent such as formic acid that can dissolve a thermoplastic resin.
[0354] Next, 100 or more glass fibers are randomly selected from the obtained insoluble components, and the total mass of the glass fibers is measured. Next, the fiber length of each glass fiber is measured by observing the glass fibers using an optical microscope, a scanning electron microscope, etc., and the value obtained by dividing the total value of the fiber length of each glass fiber by the total mass of the glass fibers can be obtained as the weight-average fiber length.
[0355] The thermoplastic resin composition obtained by the production method of the present embodiment has excellent vibration fatigue resistance and can therefore be suitably used for, for example, automobile parts, electronic and electrical parts, industrial machine parts, various gears, and the like.
[0356] Example
[0357] The present invention will be described in detail below with reference to specific examples and comparative examples, but the present invention is not limited to the following examples. It should be noted that the raw materials used in the examples and comparative examples and the measurement methods of the physical property tests and the like are as follows.
[0358] [raw material]
[0359] (A1) Crystalline polyamide
[0360] Production Example 1-1: Polyamide 66-1 (A1-1)
[0361] 15000g of equimolar salt of adipic acid and hexamethylenediamine and 0.5 mol% excess of adipic acid relative to all equimolar salt components were dissolved in 15000g of distilled water to obtain a 50% aqueous solution of the raw monomer. The obtained aqueous solution was put into an autoclave with an internal volume of 40L, and the autoclave was replaced with nitrogen. The aqueous solution was stirred at a temperature of 110°C to 150°C while slowly extracting water vapor and concentrating it to a solution concentration of 70% by mass. Then, the internal temperature was raised to 220°C. At this time, the autoclave was pressurized to 1.8MPa. This state was maintained until the internal temperature reached 270°C, and the water vapor was slowly extracted while the pressure was maintained at 1.8MPa and reacted for 1 hour.
[0362] Then, the pressure was reduced to atmospheric pressure in about 1 hour, and after reaching atmospheric pressure, it was discharged from the lower nozzle in the form of strands, water-cooled, and cut to obtain pellets of crystalline polyamide. The obtained pellets were dried at 90°C for 4 hours in a nitrogen stream. The formic acid relative viscosity of the crystalline polyamide pellets was 45, the melting point was 265°C, and the crystallization temperature was 220°C.
[0363] Production Example 1-2: Polyamide 66-2 (A1-2)
[0364] 10 kg of the pellets of the polyamide 66-1 were placed in a conical belt vacuum dryer (manufactured by Okawara Seisakusho Co., Ltd., trade name RIBOCONE RM-10V), and nitrogen was fully replaced. The pellets were heated at 190° C. for 6 hours while stirring while nitrogen was circulated at a rate of 1 L / min. Then, the temperature was lowered while nitrogen was circulated, and the pellets were taken out of the device when the temperature reached about 50° C. The formic acid relative viscosity of the pellets of the crystalline polyamide was 130.
[0365] Production Example 1-3: Polyamide 66-3 (A1-3)
[0366] Pellets were obtained in the same manner as in Production Example 1-2 except that the pellets were heated at a pellet temperature of 205° C. for 8 hours. The formic acid relative viscosity of the crystalline polyamide pellets was 250.
[0367] (B1) Glass fiber
[0368] B1-1: Glass chopped strands-1
[0369] Manufactured by Nittobo Co., Ltd., trade name "CS-3DE-456S" (glass fiber number average diameter 7 μm, glass fiber weight average length 3 mm, ignition loss 36.5, boron content 13,000 mass ppm)
[0370] B1-2: Glass chopped strands-2
[0371] Manufactured by Nippon Electric Glass Co., Ltd., trade name "ECS03T-289DE" (glass fiber number average diameter 7 μm, glass fiber weight average length 3 mm, ignition loss 13.9, boron content 14,000 mass ppm)
[0372] B1-3: Glass chopped strands-3
[0373] Manufactured by Nittobo Co., Ltd., trade name "CS-3PE-454" (glass fiber number average diameter 13 μm, glass fiber weight average length 3 mm, ignition loss 29.2, boron content 13,000 mass ppm)
[0374] B1-4: Glass chopped strands -4
[0375] The glass fibers prepared in the following manufacturing examples 1-4 (the glass fibers had a number average diameter of 7 μm, a weight average length of 3 mm, a loss on ignition of 32.7, and a boron content of 0 mass ppm)
[0376] Manufacturing Example 1-4: Glass Chopped Strands-4
[0377] A glass fiber sizing agent was obtained by diluting a polyurethane resin (trade name: VONDIC (registered trademark) 1050, an aqueous solution having a solid content of 50% by mass (manufactured by Dainippon Ink Co., Ltd.) at 2% by mass, γ-aminopropyltriethoxysilane (trade name: KBE-903, (manufactured by Shin-Etsu Chemical Co., Ltd.) at 0.6% by mass, and a lubricant [trade name: carnauba wax (manufactured by Kato Hiroko Co., Ltd.)] at 0.1% by mass with water at a ratio of 100% by mass in terms of solid content.
[0378] Glass raw materials were prepared at a ratio of SiO2: 58 mass%, Al2O3: 14 mass%, CaO: 21 mass%, MgO: 2 mass%, and Na2O+K2O: 5 mass%, and melt-spun to obtain glass long fibers with a number average fiber diameter of 7 μm, and then the glass fiber sizing agent was attached. That is, the glass fiber sizing agent was applied to the glass fibers being wound on the rotating drum using an applicator provided at a predetermined position.
[0379] Next, it was dried to obtain a roving of a glass fiber bundle surface-treated with the glass fiber sizing agent (glass fiber roving). At this time, the glass fiber was in the form of a bundle of 1000 strands. It was cut into 3 mm in length to obtain glass chopped strand-4. The chopped strand was used as glass fiber.
[0380] (C1) Ingredients
[0381] Cuprous iodide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)
[0382] (D1)Ingredients
[0383] Potassium iodide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)
[0384] Other ingredients
[0385] Antioxidant: Irganox (registered trademark) 1098 (manufactured by BASF Corporation)
[0386] Colorant: Mitsubishi (registered trademark) carbon black #2600 (manufactured by Mitsubishi Chemical Corporation)
[0387] [Example 1-1]
[0388] A twin-screw extruder (ZSK-40MC: manufactured by Coperion (Germany)) was used as the extruder. The twin-screw extruder has an upstream supply port provided on the first barrel from the upstream side and a downstream supply port provided on the eighth barrel from the upstream side. Moreover, L / D (barrel length of the extruder / barrel diameter of the extruder) = 48 (number of barrels: 12). In the twin-screw extruder, the temperature from the upstream supply port to the previous barrel of the barrel having the downstream supply port is set to 310°C to 320°C, the temperature from the barrel having the downstream supply port to the last barrel is set to 290°C, the screw speed is set to 200rpm, the discharge volume is set to 80kg / hour, and the degree of decompression is set to -0.08MPa.
[0389] Under these conditions, (A1) crystalline polyamide, (C1) component, (D1) component and other components were supplied from the upstream supply port in a ratio to form the composition described in Table 1, and (B1) glass fiber was supplied from the downstream supply port in a manner to form the composition described in Table 1, and melt-kneading was carried out to produce pellets of a resin composition.
[0390] 11 kg of the obtained pellets were placed in a thermostat (manufactured by ESPEC Co., Ltd., trade name Perfect Oven PHH-202M) and fully purged with nitrogen. Solid phase polymerization was performed by heating the pellets at 210° C. for 2 hours while nitrogen was flowing at a rate of 1 L / min. Then, the temperature was lowered while nitrogen was flowing, and the pellets were taken out of the device in a pellet state when the temperature reached about 50° C.
[0391] The obtained pellets were molded into a test piece of multi-purpose test piece type A of ISO 3167 using an injection molding machine PS-40E [manufactured by Nissei Plastic Co., Ltd.], with the mold temperature set to 80°C and the barrel temperature set to 290°C. Various mechanical properties, vibration fatigue properties, wear properties, etc. were evaluated using the molded piece. In addition, the molar ratio of the content of the copper element to the content of the halogen element was calculated as I / Cu from the usage ratio of copper (I) iodide and potassium iodide.
[0392] [Examples 1-2 to 1-18]
[0393] Except for changing the types, contents or solid phase polymerization times of (A1) crystalline polyamide, (B1) glass fiber, (C1) component, (D1) component and other components as shown in Tables 1 to 4, the same operation as in Example 1-1 was carried out to prepare pellets and test pieces of the resin compositions of Examples 1-2 to 1-18 for various tests.
[0394] It should be noted that in Tables 1 to 4, the masterbatch containing the (C1) component and the (D1) component is abbreviated as "C1 / D1 masterbatch". The C1 / D1 masterbatch is obtained by blending 90 parts by mass of polyamide 6 (SF1013A manufactured by Ube Industries, Ltd.), 1.8 parts by mass of the (C1) component and 18 parts by mass of the (D1) component and melt-kneading them using a twin-screw extruder (TEM35φ twin-screw extruder manufactured by Toshiba Machine Co., Ltd.) at a screw speed of 200 rpm and a discharge volume of 90 kg / hour. Melt kneading using a twin-screw extruder can be stably implemented. The molar ratio of the halogen content to the copper content in the C1 / D1 masterbatch (halogen / copper) is 12 / 1.
[0395] [Comparative Examples 1-1 to 1-5]
[0396] Using the same twin-screw extruder as in Example 1-1, the temperature from the upstream supply port to the die head was set to 300°C, the screw speed was set to 200 rpm, and the discharge volume was set to 15 kg / hour. Under this condition, (A1) crystalline polyamide, (C1) component, (D1) component and other components were supplied from the upstream supply port in a manner to form the composition described in Tables 5 to 6, and (B1) glass fiber was supplied from the downstream supply port in a manner to form the composition described in Tables 5 to 6, and melt-kneaded, thereby producing pellets of the resin composition. Using the same injection molding machine as in Example 1-1, the mold temperature was set to 80°C, the barrel temperature was set to 290°C, and the pellets of the obtained resin composition were molded into a test piece of the multi-purpose test piece type A of ISO3167. Various mechanical properties, vibration fatigue properties, wear properties, etc. were evaluated using the molded piece.
[0397] [Comparative Examples 1-6]
[0398] Using the same twin-screw extruder as in Example 1-1, the temperature from the upstream supply port to the die head was set to 300°C, the screw speed was set to 200 rpm, and the discharge volume was set to 15 kg / hour. Under this condition, (A1) crystalline polyamide, (C1) component, (D1) component and other components were supplied from the upstream supply port in a manner to form the composition described in Table 6, and (B1) glass fiber was supplied from the downstream supply port in a manner to form the composition described in Table 6, and melt-kneaded, thereby preparing pellets of the resin composition. 11 kg of the obtained pellets were placed in a conical belt vacuum dryer (manufactured by Ohkawara Seisakusho Co., Ltd., trade name RIBOCONE RM-10V) and fully purged with nitrogen. Solid phase polymerization was carried out by heating the pellets at a temperature of 210°C for 2 hours while stirring while nitrogen was circulated at a rate of 1 L / min. Then, the temperature was lowered while nitrogen was circulated, and the pellets were taken out from the device when the temperature reached about 50°C. The pellets of the resin composition obtained were molded into a test piece of multi-purpose test piece type A of ISO 3167 using the same injection molding machine as in Example 1-1, with the mold temperature set to 80°C and the barrel temperature set to 290°C. The molded pieces were used to evaluate various mechanical properties, vibration fatigue properties, wear properties, etc.
[0399] [Example 1-19]
[0400] The pellets of the resin composition obtained in Example 1-8 were injection molded using an injection molding machine α50i-A [manufactured by FANUC Corporation], with the barrel temperature set to 290°C, under the injection conditions of a mold temperature of 80°C, a maximum injection pressure of 120 MPa, an injection time of 10 seconds, and a cooling time of 60 seconds, thereby obtaining a worm gear having a modulus of 3.0, a number of teeth of 50, a tooth thickness of 5 mm, and a tooth width of 15 mm. The gear durability test was performed using the worm gear.
[0401] [Examples 1-20, 1-21; Comparative Examples 1-7, 1-8]
[0402] Worm gears were molded from the pellets of the resin compositions of Example 1-11, Example 1-1, Comparative Example 1-2, and Comparative Example 1-6 in the same manner as in Example 1-19, except that the resin composition used was changed to the pellets of the resin composition described in Table 7, and were subjected to various tests.
[0403] [Measurement method]
[0404] <Ignition loss of glass fiber (amount of surface treatment agent attached)>
[0405] 10g of glass fiber was accurately weighed and then heated in an electric furnace at 650°C for 1 hour. The mass loss during this period was taken as the ignition loss of the glass fiber. This operation was performed 10 times for different glass fibers at 10g each time, and the average value M and standard deviation σ of the ignition loss were calculated.
[0406] <Formic acid relative viscosity VR>
[0407] The formic acid relative viscosity (VR) is obtained by comparing the viscosity of a solution (soluble component) prepared by dissolving the fiber-reinforced polyamide resin composition obtained in the examples and comparative examples in formic acid with the viscosity of formic acid itself. Specifically, it is implemented according to ASTM-D789. More specifically, VR is measured at 25° C. using a solution obtained by dissolving the fiber-reinforced polyamide resin composition in 90% by mass formic acid (10% by mass of water) at a ratio of 8.4% by mass of the soluble component in the fiber-reinforced polyamide resin composition.
[0408] <Quantification of formic acid insoluble components>
[0409] The formic acid-insoluble content of the polyamide resin compositions produced in Examples 1-1 to 1-18 and Comparative Examples 1-1 to 1-6 was determined as follows.
[0410] First, a fiber-reinforced polyamide resin composition was added to 90% by mass of formic acid (10% by mass of water), and dissolved while stirring for one day and night to obtain a solution. The obtained solution was filtered using a membrane filter with a pore size of 0.65 μm to separate the formic acid-insoluble components remaining on the filter paper. The residual solvent was removed from the separated formic acid-insoluble components by air-drying for one day and night, and the mass of the obtained dry product was measured, thereby calculating the formic acid-insoluble component amount by the following formula.
[0411] Formic acid insoluble matter (mass %) = dry mass (g) / fiber-reinforced polyamide resin composition dissolved in formic acid (g) × 100
[0412] In addition, the ash content in the sample was measured in advance based on the provisions of ISO3451-4, and the amount of formic acid insoluble components relative to the ash content was calculated by the following formula.
[0413] Formic acid insoluble matter (mass %) relative to ash content = formic acid insoluble matter (mass %) / ash content (mass %) × 100
[0414] The formic acid insoluble content relative to the ash content was measured 10 times by the above method, and the average value was calculated.
[0415] <Short GF ratio>
[0416] The pellets of the glass fiber reinforced polyamide resin composition obtained in Examples 1-1 to 1-18 and Comparative Examples 1-1 to 1-6 were heated at 650°C for 2 hours to burn and remove only the polyamide, followed by observation using an optical microscope, and the lengths of 400 randomly selected reinforcing fibers were measured using an image analyzer, and the ratio of glass fibers of 250 μm or less was calculated.
[0417] <Number of undissolved fibers>
[0418] 1 kg of the pellets of the glass fiber reinforced polyamide resin composition obtained in Examples 1-1 to 1-18 and Comparative Examples 1-1 to 1-6 were weighed, and then the pellets in which the glass fiber bundles protruded from the cross section of the pellets by more than 0.5 mm were classified as undefibrated pellets, and the number of undefibrated pellets was counted. It should be noted that this operation was performed 10 times for different pellets at 1 kg each, and the average value was taken as the number of undefibrated pellets.
[0419] <Tensile test>
[0420] Using the A-type test pieces obtained in Examples 1-1 to 1-18 and Comparative Examples 1-1 to 1-6, a tensile test was performed at a test speed of 50 mm / min in accordance with ISO527, and the tensile strength (MPa) was measured.
[0421] In addition, a total of 20 A-type test pieces were molded, and the tensile strength of each piece was measured. The coefficient of variation (CV) of the tensile strength was calculated using the following formula: 拉伸 ).
[0422] CV 拉伸 =(σ 拉伸 / μ 拉伸 )×100
[0423] Here, σ 拉伸 represents the standard deviation of tensile strength, μ 拉伸 It represents the arithmetic mean of tensile strength.
[0424] <Vibration fatigue>
[0425] Using an injection molding machine PS-40E [manufactured by Nissei Plastic Co., Ltd.], the injection + holding time was set to 10 seconds, the mold temperature was set to 80°C, and the barrel temperature was set to 290°C. According to ISO294-1, JIS K7139 small ISO test pieces (thickness 3 mm) were prepared using the resin composition pellets obtained in Examples 1-1 to 1-18 and Comparative Examples 1-1 to 1-6. The test pieces were used as objects and a vibration fatigue test was performed using a Shimadzu servo pulse generator (EHF-FV1OKN-1 OLA) manufactured by Shimadzu Corporation. The conditions at this time were set to frequency: 20 Hz, waveform: sine wave, temperature: 120°C, stress ratio: 0.1, chuck distance: 30 mm, and stress applied to the sample: 60 MPa, and the number of vibrations until the sample broke was determined.
[0426] <Friction coefficient and wear depth>
[0427] Using a reciprocating friction and wear tester (AFT-15MS manufactured by Toyo Seimitsu Co., Ltd.) and a SUS304 test piece (a ball with a diameter of 5 mm) as a counter material, a sliding test was performed on the A-type test pieces obtained in Examples 1-1 to 1-18 and Comparative Examples 1-1 to 1-6 under the conditions of a linear speed of 30 mm / sec, a reciprocating distance of 20 mm, a temperature of 23°C, a humidity of 50%, a load of 1.5 kg, and a reciprocating number of 5,000 times to obtain the friction coefficient. The wear depth of the central part of the wear scar of the sample after the sliding test was measured using a surface roughness meter (575A-30 manufactured by Toyo Seimitsu Co., Ltd.). The respective results are indicated as "friction coefficient (23°C)" and "wear depth (23°C)" in Tables 8 to 13.
[0428] <Black spot foreign matter>
[0429] Using an injection molding machine (FN-3000, screw diameter 40 mm, manufactured by Nissei Resin Industry Co., Ltd.), the resin composition pellets obtained in Examples 1-1 to 1-18 and Comparative Examples 1-1 to 1-6 were injection molded under the molding conditions of barrel temperature 290°C, mold temperature 80°C, injection pressure 65 MPa, injection time 15 seconds, cooling time 15 seconds and screw speed 200 rpm to form a flat plate with a width of 80 mm × length of 120 mm × thickness of 8 mm, and the number of black spot foreign matter was measured.
[0430] <Gear durability test>
[0431] The test was carried out using the worm gears obtained in Examples 1-19 to 1-21 and Comparative Examples 1-7 to 1-8 and using a gear durability testing machine manufactured by Toshiba Machine Co., Ltd. A SUS304 worm and a resin worm gear were combined, with the worm gear on the driving side and the worm gear on the driven side. In addition, grease (Multemp CPL, manufactured by Kyodo Yushi Co., Ltd.) was applied to the meshing part, and it was rotated by hand so that the grease was blended with the worm and worm gear as a whole. Next, the gear on the driving side was rotated under the following conditions, and the number of times until the gear was broken (durability number) was measured.
[0432] Test conditions: temperature 23°C, humidity 50%, torque 25N / m, rotation speed 30rpm
[0433] After the forward and return paths rotate once each, a 1-second interval is allowed before the rotation in the opposite direction is performed.
[0434] <Mass reduction rate after 100,000 rotations>
[0435] The worm gears obtained in Examples 1-9 to 1-21 and Comparative Examples 1-7 to 1-8 were rotated 100,000 times (1.0×10 5 The weight W1 of the worm gear was then measured, and the weight reduction rate (mass %) relative to the weight W0 before the start of the test was calculated according to the following formula.
[0436] Weight reduction rate = [(W0-W1) / W0] × 100
[0437] [Table 1]
[0438]
[0439] [Table 2]
[0440]
[0441] [Table 3]
[0442]
[0443] [Table 4]
[0444]
[0445] [Table 5]
[0446]
[0447] [Table 6]
[0448]
[0449] [Table 7]
[0450]
[0451] [Table 8]
[0452]
[0453] [Table 9]
[0454]
[0455] [Table 10]
[0456]
[0457] [Table 11]
[0458]
[0459] [Table 12]
[0460]
[0461] [Table 13]
[0462]
[0463] The worm gears of Examples 1-19 to 1-21 satisfying the prescribed ranges were provided with sufficient mechanical properties, with reduced property variations, and with sliding characteristics.
[0464] On the other hand, the worm gears of Comparative Examples 1-7 and 1-8 did not impart sufficient mechanical properties to the molded products, nor did they reduce property variations and did not impart sliding properties.
[0465] [Raw materials of each sample]
[0466] (A2) Production of polyamide resin
[0467] (Production Example 2-1: Production of Polyamide Resin A2-1 (Polyamide 66))
[0468] 15,000g of an equimolar salt of adipic acid and hexamethylenediamine and an excess of 0.5 mol% of adipic acid relative to the equimolar salt component were dissolved in 15,000g of distilled water to obtain a 50% aqueous solution of the raw monomer. The obtained aqueous solution was put into an autoclave with an internal volume of 40L, and the autoclave was replaced with nitrogen. While stirring the aqueous solution at a temperature of 110°C or more and 150°C or less, water vapor was slowly extracted and concentrated to a solution concentration of 70% by mass. Then, the internal temperature was raised to 220°C. At this time, the autoclave was pressurized to 1.8MPa. This state was maintained until the internal temperature reached 270°C, and water vapor was slowly extracted while the pressure was maintained at 1.8MPa and reacted for 1 hour. Then, the pressure was reduced to atmospheric pressure in about 1 hour, and after reaching atmospheric pressure, it was discharged from the lower nozzle in the form of strands, and water-cooled and cut to obtain pellets of polyamide resin A2-1.
[0469] The obtained pellets were dried in a nitrogen stream at 90°C for 4 hours. The pellets had a viscosity number RV of 48 and a melting point of 265°C.
[0470] (Production Example 2-2: Production of Polyamide Resin A2-2 (Polyamide 66))
[0471] In addition to using a vacuum device to press the inside of the tank at 100 Torr (1.33×10 4 Pellets of polyamide resin A2-2 were produced by the same method as in Production Example 2-1 except that the reduced pressure of 1.404 Pa (0.0247 W) was maintained for 5 minutes.
[0472] The pellets had a viscosity number RV of 60 and a melting point of 264°C.
[0473] (Production Example 2-3: Production of Polyamide Resin A2-3 (Polyamide 66))
[0474] 10 kg of the pellets obtained in the above (Manufacturing Example 2-1) were placed in a conical belt vacuum dryer (manufactured by Okawara Seisakusho Co., Ltd., trade name RIBOCONE RM-10V), and nitrogen was purged while stirring while nitrogen was circulated at a rate of 10 L / min. The pellets were heated at a temperature of 215°C for 6 hours while stirring while nitrogen was circulated at a rate of 10 L / min. Then, the temperature was lowered while nitrogen was circulated, and the pellets were taken out of the device in the form of pellets when the temperature reached about 50°C. The viscosity number RV of the pellets was 260, and the melting point was 262°C.
[0475] (B2) Manufacture of fibrous reinforcement materials
[0476] (Manufacturing Example 2-4: Manufacture of Fibrous Reinforcement Material B2-1)
[0477] First, (x2-1) to (x2-4) described later were diluted with water so that, on a solid basis, 2% by mass of a polyurethane resin, 4% by mass of a maleic anhydride-butadiene copolymer, 0.6% by mass of γ-aminopropyltriethoxysilane, and 0.1% by mass of a carnauba wax were contained, thereby obtaining a glass fiber sizing agent.
[0478] The obtained glass fiber sizing agent is attached to glass fibers having a number average fiber diameter of 7 μm. The attachment method is a method of attaching the sizing agent to the glass fibers using an applicator disposed midway in winding the melt-spun glass fibers on a rotating drum. Then, the glass fibers attached with the sizing agent are dried to obtain rovings of glass fiber bundles surface-treated with the above-mentioned glass fiber sizing agent. At this time, the glass fibers form bundles of 1,000. The amount of glass fiber sizing agent attached to the glass fibers is 0.6% by mass. The obtained rovings are cut into a length of 3 mm to obtain a fibrous reinforcing material B2-1 (chopped strands, hereinafter referred to as "(B2-1)").
[0479] In addition, the components (x2-1) to (x2-4) constituting the sizing agent used when producing the above-mentioned fibrous reinforcing material are as follows.
[0480] (x2-1) Polyurethane resin emulsion
[0481] Trade name: VONDIC (registered trademark) 1050 (manufactured by Dainippon Ink Co., Ltd.)
[0482] (solid content 50% by mass aqueous solution)
[0483] (x2-2) Maleic anhydride copolymer emulsion
[0484] Product name: ACROBINDER (registered trademark) BG-7 (manufactured by Sanyo Chemical Industries, Ltd.)
[0485] (solid content 25% by mass aqueous solution)
[0486] (x2-3) Aminosilane coupling agent
[0487] Trade name: KBE-903 (manufactured by Shin-Etsu Chemical Co., Ltd.)
[0488] γ-Aminopropyltriethoxysilane
[0489] (x2-4) Lubricant
[0490] Product name: Carnauba wax (manufactured by Kato Yoko Co., Ltd.)
[0491] (Manufacturing Example 2-5: Manufacture of Fibrous Reinforcement Material B2-2)
[0492] A fibrous reinforcing material B2-2 (chopped strands, hereinafter also referred to as "(B2-2)") was obtained by the same method as in the above-mentioned manufacturing example 2-4, except that glass fibers having a number average fiber diameter of 5 μm were used instead of glass fibers having a number average fiber diameter of 7 μm. The amount of the glass fiber sizing agent attached to the glass fibers was 0.7% by mass.
[0493] (Manufacturing Example 2-6: Manufacture of Fibrous Reinforcement Material B2-3)
[0494] A fibrous reinforcing material (B2-3) (chopped strands, hereinafter also referred to as "(B2-3)") was obtained in the same manner as in Production Example 2-4 except that glass fibers having a number average fiber diameter of 13 μm were used instead of glass fibers having a number average fiber diameter of 7 μm. The amount of the glass fiber sizing agent attached to the glass fibers was 0.4% by mass.
[0495] [Other raw materials for each sample]
[0496] In addition to the above-mentioned raw materials, the following raw materials were used.
[0497] (C2) Copper compounds
[0498] Cuprous iodide: Cuprous iodide (I), manufactured by Wako Pure Chemical Industries, Ltd.
[0499] (D2) Metal Halide
[0500] Potassium iodide: Potassium iodide, manufactured by Wako Pure Chemical Industries, Ltd.
[0501] <Examples 2-1 to 2-7, Comparative Examples 2-1 to 2-2>
[0502] Using the above-mentioned components, polyamide resin compositions of various samples were produced under the conditions shown below.
[0503] [Example 2-1: Production of polyamide resin composition PA-a1]
[0504] (1) Melt-kneading process
[0505] A twin-screw extruder (manufactured by Coperion Corporation, trade name "ZSK26MC") having a screw diameter of 26 mm was used. A screw equipped with a melting zone and a kneading zone was used. According to the formulation described in Table 14, a mixture obtained by adding a copper compound and a halide to the polyamide resin A2-1 obtained in Preparation Example 2-1 was supplied in a top feeding manner, and the fibrous reinforcing material B2-1 obtained in Preparation Example 2-4 was supplied in a side feeding manner. Melt kneading was carried out under the extrusion conditions of a set temperature of 290°C, a screw speed of 300 rpm, and a discharge rate of 29 kg / hour. The pellets were cooled to the strand water immersion length described in Table 14, and cut with a strand cutter to obtain pellets. The shape of the obtained pellets was an elliptical cylinder, and the pellet length, major diameter a, minor diameter b, and ratio a / b were described in Table 17.
[0506] (2) Heating process (solid phase polymerization)
[0507] 11 kg of the pellets obtained in the above-mentioned (1) melt kneading step were placed in a conical belt vacuum dryer (manufactured by Ohkawara Seisakusho Co., Ltd., trade name RIBOCONE RM-10V), and nitrogen replacement was performed while stirring at a rate of 10 L / min. The pellets were heated at a temperature of 210°C for 5 hours while stirring while nitrogen was flowing at a rate of 10 L / min. Then, the temperature was lowered while nitrogen was flowing, and the pellets were taken out from the device in the form of pellets when the temperature reached about 50°C, thereby obtaining pellets of the polyamide resin composition PA-a1. The viscosity number RV of the obtained pellets was 177.
[0508] [Example 2-2: Production of polyamide resin composition PA-a2]
[0509] Except for shortening the strand water immersion length, melt kneading and solid phase polymerization were carried out in the same manner as in Example 2-1 to obtain pellets of the polyamide resin composition PA-a2. The pellet length, major diameter a, minor diameter b and ratio a / b after melt kneading are shown in Table 17. The viscosity number RV of the pellets obtained after solid phase polymerization was 184.
[0510] [Example 2-3: Production of polyamide resin composition PA-a3)
[0511] Except that the polyamide resin A2-2 obtained in Preparation Example 2-2 was used instead of the polyamide resin A2-1 obtained in Preparation Example 2-1, melt kneading and solid phase polymerization were carried out in the same manner as in Example 2-1 to obtain pellets of a polyamide resin composition PA-a3. The pellet length, major diameter a, minor diameter b and ratio a / b after melt kneading are shown in Table 17. The viscosity number RV of the pellets obtained after solid phase polymerization was 185.
[0512] [Example 2-4: Production of polyamide resin composition PA-a4]
[0513] Except that the compounding amount of the fibrous reinforcing material B2-1 was reduced to the amount shown in Table 14, melt kneading and solid phase polymerization were carried out in the same manner as in Example 2-1 to obtain pellets of the polyamide resin composition PA-a4. The pellet length, major diameter a, minor diameter b and ratio a / b after melt kneading are shown in Table 17. The viscosity number RV of the pellets obtained after solid phase polymerization was 180.
[0514] [Example 2-5: Production of polyamide resin composition PA-a5]
[0515] Except that the compounding amount of the fibrous reinforcing material B2-1 was increased to the amount shown in Table 15, melt kneading and solid phase polymerization were carried out in the same manner as in Example 2-1 to obtain pellets of the polyamide resin composition PA-a5. The pellet length, major diameter a, minor diameter b and ratio a / b after melt kneading are shown in Table 18. The viscosity number RV of the pellets obtained after solid phase polymerization was 176.
[0516] [Example 2-6: Production of polyamide resin composition PA-a6]
[0517] Except that fibrous reinforcement B2-2 was used instead of fibrous reinforcement B2-1, melt kneading and solid phase polymerization were carried out in the same manner as in Example 2-1 to obtain pellets of polyamide resin composition PA-a6. The pellet length, major diameter a, minor diameter b and ratio a / b after melt kneading are shown in Table 18. The viscosity number RV of the pellets obtained after solid phase polymerization was 178.
[0518] [Example 2-7: Production of polyamide resin composition PA-a7]
[0519] Except that fibrous reinforcement B2-3 was used instead of fibrous reinforcement B2-1, melt kneading and solid phase polymerization were carried out in the same manner as in Example 2-1 to obtain pellets of polyamide resin composition PA-a7. The pellet length, major diameter a, minor diameter b and ratio a / b after melt kneading are shown in Table 18. The viscosity number RV of the pellets obtained after solid phase polymerization was 177.
[0520] [Comparative Example 2-1: Production of polyamide resin composition PA-b1]
[0521] Except that the strand water immersion length was extended, melt kneading and solid phase polymerization were carried out in the same manner as in Example 2-1 to obtain pellets of the polyamide resin composition PA-b1. The pellet length, major diameter a, minor diameter b and ratio a / b after melt kneading are shown in Table 19. The viscosity number RV of the pellets obtained after solid phase polymerization was 170.
[0522] [Comparative Example 2-2: Production of polyamide resin composition PA-b2]
[0523] The polyamide resin A2-3 obtained in Preparation Example 2-3 was used instead of the polyamide resin A2-1 obtained in Preparation Example 2-1. According to the compounding composition described in Table 16, the mixture obtained by adding the copper compound and the halide was supplied in a top feeding manner, and the fibrous reinforcing material B2-1 obtained in Preparation Example 2-4 was supplied in a side feeding manner. Melt kneading was carried out under the extrusion conditions of a set temperature of 310° C., a screw speed of 200 rpm, and a discharge rate of 15 kg / hour. The strands were cooled to the strand water immersion length described in Table 16, and cut by a strand cutter to obtain pellets of the polyamide resin composition PA-b2. The shape of the obtained pellets was an elliptical cylinder, and the pellet length, major diameter a, minor diameter b, and ratio a / b were described in Table 19. The viscosity number RV of the obtained pellets was 180.
[0524] <Evaluation>
[0525] The polyamide resin composition of each sample obtained by the above method was evaluated as follows. The evaluation results are shown in Tables 17 to 19.
[0526] (1) Pellet shape
[0527] For 100 pellets of the polyamide resin composition obtained in the examples and comparative examples, the major diameter a, the minor diameter b and the pellet length of the pellet cross section were measured using an electronic caliper, and the respective average values were taken as the major diameter a, the minor diameter b and the pellet length. In addition, the ratio a / b of the major diameter a and the minor diameter b of the pellet cross section was calculated.
[0528] (2) Viscosity number RV
[0529] The relative viscosity RV of the polyamide resin compositions obtained in Examples and Comparative Examples was measured according to ASTM D789. More specifically, the RV value was measured at 25° C. using a solution obtained by dissolving the polyamide at 8.4% by mass in 90% by mass formic acid (10% by mass water).
[0530] (3) Molecular weight
[0531] The proportion (%) of components having a molecular weight of 10,000 or less and the proportion (%) of components having a molecular weight of 250,000 or more of the polyamide resin compositions obtained in Examples and Comparative Examples were calculated from molecular weight distributions measured by the following gel permeation chromatography (GPC).
[0532] Device: HLC-8320GPC manufactured by Tosoh Corporation
[0533] Detector: Differential Refractometer (RI)
[0534] Solvent: 0.1 mol% sodium trifluoroacetate dissolved in hexafluoroisopropanol (HFIP)
[0535] Column: Two "TSKgel-GMHHR-M" and one "G1000HHR" manufactured by Tosoh Corporation were connected in series and used. The amount was calculated by conversion to polymethyl methacrylate (PMMA) based on the obtained elution curve.
[0536] (4) Molar ratio of the amount of carboxyl terminal groups to the amount of amino terminal groups
[0537] The polyamide resin compositions obtained in the examples and comparative examples were 1 H-NMR (sulfuric acid-d2 solvent) calculates the amount of carboxyl terminal groups [COOH] and amino terminal groups [NH2] as the amount of terminal groups present in 1 kg of polyamide resin. The specific procedure is shown below.
[0538] Carboxyl terminal: The hydrogen of the methylene group (-CH2-) adjacent to the terminal COOH was calculated using the integrated value of the peak (a') at 2.724 ppm.
[0539] Amino terminal: The hydrogen of the methylene group (-CH2-) adjacent to the terminal NH2 was calculated using the integrated value of the peak (b') near 2.884 ppm.
[0540] Dicarboxylic acid unit in the main chain of polyamide: Calculated using the integrated value of the peak (a) at 2.451 ppm with respect to the hydrogen of the methylene group (-CH2-) adjacent to the amide group.
[0541] Diamine unit in the main chain of the polyamide: The hydrogen of the methylene group (-CH2-) adjacent to the amide group was calculated using the integrated value of the peak (b) at 3.254 ppm.
[0542] The carboxyl terminal group amount [COOH] and the amino terminal group amount [NH2] were calculated using the integrated values of the peaks and the following formulas.
[0543] Carboxyl terminal group content [COOH] (mmol Eq / kg)
[0544] =(a' / 2) / [{(b+b')×114.2 / 4}+{(a+a')×112.1 / 4}]
[0545] Amino terminal group content [NH2] (mmol Eq / kg)
[0546] =(b' / 2) / [{(b+b')×114.2 / 4}+{(a+a')×112.1 / 4}]
[0547] Then, the molar ratio [NH2] / [COOH] of the amount of the carboxyl terminal group to the amount of the amino terminal group is calculated from the obtained amount of the carboxyl terminal group [COOH] and the amount of the amino terminal group [NH2].
[0548] [Table 14]
[0549]
[0550] [Table 15]
[0551]
[0552] [Table 16]
[0553]
[0554] [Table 17]
[0555]
[0556] [Table 18]
[0557]
[0558] [Table 19]
[0559]
[0560] From the results of Tables 17 to 19, it can be seen that for the polyamide resin compositions PA-a1 to PA-a7 (Examples 2-1 to 2-7), although the heating step (solid phase polymerization) time was set to be constant, the high molecular weight component increased and the viscosity number RV value also became higher. It can be seen that by using elliptical columnar pellets to carry out the heating step (solid phase polymerization), the molecular weight distribution is effectively shifted to the polymer side, so the heating step (solid phase polymerization) time can be shortened.
[0561] <Measurement methods of physical properties>
[0562] [Physical Properties 3-1]
[0563] (Viscosity number VN)
[0564] The viscosity number VN was measured using pellets of polyamide, melt-kneaded product, and thermoplastic resin composition in accordance with ISO307 (JIS-K6933). Specifically, the viscosity number VN was measured in a solution of polyamide, melt-kneaded product, or thermoplastic resin composition at a concentration of 0.5% by mass in sulfuric acid at a concentration of 96% by mass at 25°C. When a reinforcing material such as glass fiber is included in the sample, the ash content in the sample is measured in advance based on the provisions of ISO3451-4, for example, and the content of the polyamide resin after deducting the ash content is used to calculate the content of the polyamide resin in the sample.
[0565] [Physical Properties 3-2]
[0566] (Water content)
[0567] The pellets of the melt-kneaded products produced in Examples and Comparative Examples were measured for water content (mass %) in accordance with ISO15512 using a Karl Fischer moisture meter (manufactured by Mitsubishi Chemical Analysis Tech Co., Ltd., coulometric moisture meter CA-200).
[0568] [Physical Properties 3-3]
[0569] (Melting Point)
[0570] According to JIS-K7121, the heat of fusion (hereinafter also referred to as "DSC measurement") was measured using Diamond-DSC manufactured by PERKIN-ELMER. The DSC measurement was performed under a nitrogen atmosphere. About 10 mg of pellets of polyamide 66 manufactured in Manufacturing Examples 3-1 and 3-2 were used as samples. Specifically, in the above-mentioned DSC measurement, first, the sample was heated from 25°C to the melting point of the polyamide + about 30°C (for example, 294°C for PA66) at a heating rate of 20°C / min. Then, the highest temperature during the first heating was maintained for 3 minutes to temporarily completely melt the polyamide. Then, the sample was cooled to 25°C at a cooling rate of 20°C / min and maintained at 25°C for 3 minutes. Then, the sample was heated again at a heating rate of 20°C / min in the same manner, and the melting point of polyamide 66 was obtained based on the endothermic peak (melting peak) that appeared at this time.
[0571] [Physical Properties 3-4]
[0572] (Weight average fiber length of glass fiber)
[0573] The weight average fiber length of the glass fiber contained in the polyamide resin composition after the heating process is calculated by the method described below. 1g of the polyamide resin composition after the heating process is collected in a porcelain crucible, and the resin composition is burned and removed using an electric muffle furnace (FP-31 type manufactured by Yamato Science Co., Ltd., set at 600°C). The glass fiber remaining after burning is transferred to a slide glass, observed under an optical microscope, and the length of 400 randomly selected glass fibers is measured using an image analysis device. Based on the obtained value, the value obtained by dividing the total value by the total mass of the glass fibers is calculated as the weight average fiber length.
[0574] <Evaluation Method>
[0575] [Preparation of test pieces]
[0576] For the pellets of the thermoplastic resin composition manufactured in the examples and comparative examples, small tensile test pieces (type CP13) (thickness 3 mm) were manufactured as follows according to JIS-K7139 using an injection molding machine. PS40E manufactured by Nissei Plastic Industry Co., Ltd. was used as an injection molding device, and a mold for obtaining two of the above-mentioned small tensile test pieces was installed. It should be noted that the barrel temperature was set to the melting point of the polyamide + about 15°C (for example, 280°C for PA66), and the mold temperature was set to 80°C. In addition, under the injection molding conditions of injection for 10 seconds, cooling for 7 seconds, and plasticization amount of 30 mm (buffer amount of about 10 mm), dumbbell-shaped small tensile test pieces were obtained from the pellets of the thermoplastic resin composition.
[0577] [Evaluation 3-1]
[0578] (Color tones of pellets and molded products)
[0579] The L value, a value, and b value were measured by reflection measurement using a colorimeter ZE2000 manufactured by Nippon Denshoku Industries Co., Ltd., and the yellowness was determined by the b value. When the b value is -, the larger the absolute value, the whiter and better the color tone is, and when the b value is +, the larger the absolute value, the more yellow coloration occurs.
[0580] [Evaluation 3-2]
[0581] (Vibration fatigue resistance)
[0582] For the obtained small tensile test piece (type CP13) (thickness 3 mm), according to JIS K7118, a hydraulic servo fatigue testing machine (trade name: EHF-50-10-3, manufactured by Saginomiya Manufacturing Co., Ltd.) was used to determine the number of vibrations (times) when the test piece broke under the conditions of a temperature of 120°C, a sine wave frequency of 20 Hz, and a tensile load of 60 MPa.
[0583] As the evaluation standard, the more vibrations until the fracture, the better (in the case of 15×10 5 times or more), the vibration fatigue resistance was evaluated to be more excellent.
[0584] [Productivity Evaluation: Abnormal Noise Evaluation during Solid Phase Polymerization]
[0585] During the solid phase polymerization operation, 10 persons confirmed the occurrence of roaring sound and abnormal noise, and evaluated it as follows.
[0586] When the number of people determined to have generated a roaring sound or abnormal noise is 0: ○ (good)
[0587] When the number of people determined to have generated the roaring sound / abnormal noise is 1 or more and 2 or less: △ (bad)
[0588] When the number of people determined to have generated the roaring sound or abnormal noise is 3 or more: × (extremely bad)
[0589] <Raw materials>
[0590] 1. (A3) Ingredients: Polyamide production
[0591] [Production Example 3-1]
[0592] (Polyamide A3-1: Production of polyamide 66)
[0593] 15,000g of an equimolar salt of adipic acid and hexamethylenediamine and an excess of 0.5 mol% of adipic acid relative to the equimolar salt component were dissolved in 15,000g of distilled water to obtain a 50% aqueous solution of the raw monomer. The obtained aqueous solution was put into an autoclave with an internal volume of 40L, and the autoclave was replaced with nitrogen. While stirring the aqueous solution at a temperature of 110°C or more and 150°C or less, water vapor was slowly extracted and concentrated to a solution concentration of 70% by mass. Then, the internal temperature was raised to 220°C. At this time, the autoclave was pressurized to 1.8MPa. This state was maintained until the internal temperature reached 270°C, and water vapor was slowly extracted while the pressure was maintained at 1.8MPa and reacted for 1 hour. Then, the pressure was reduced to atmospheric pressure in about 1 hour, and after reaching atmospheric pressure, it was discharged from the lower nozzle in the form of strands, and water-cooled and cut to obtain pellets of polyamide A3-1. The obtained pellets were dried in a nitrogen stream at 90°C for 4 hours. The pellets had a viscosity number VN of 133 and a melting point of 265°C.
[0594] [Production Example 3-2]
[0595] (Polyamide A3-2: Production of polyamide 66)
[0596] In addition to using a vacuum device to press the inside of the tank at 100 Torr (1.33×10 4 Pellets of polyamide A3-2 were produced in the same manner as in Production Example 3-1 except that the mixture was kept under reduced pressure of 100 Pa for 10 minutes. The viscosity number VN of the pellets was 182 and the melting point was 264°C.
[0597] 2. (B3) Components: Manufacturing of glass fiber
[0598] [Production Example 3-3]
[0599] (Manufacture of glass fiber B3-1)
[0600] First, (x3-1) to (x3-4) described later were diluted with water at a ratio of 2% by mass of a polyurethane resin, 4% by mass of a maleic anhydride-butadiene copolymer, 0.6% by mass of γ-aminopropyltriethoxysilane, and 0.1% by mass of a carnauba wax in terms of solid content, thereby obtaining a glass fiber sizing agent.
[0601] The obtained glass fiber sizing agent is attached to glass fibers (containing boron oxide) having a number average fiber diameter of 7 μm. The attachment method is a method of attaching the sizing agent to the glass fibers using an applicator disposed midway in the process of winding the melt-spun glass fibers on a rotating drum. Then, the glass fibers to which the sizing agent is attached are dried, thereby obtaining a roving of a glass fiber bundle surface-treated with the above-mentioned glass fiber sizing agent. At this time, the glass fibers form a bundle of 1,000 fibers. The amount of the glass fiber sizing agent attached to the glass fibers is 0.6% by mass. The obtained roving is cut into a length of 3 mm to obtain glass fiber B3-1 (chopped strands, hereinafter also referred to as "(B3-1)").
[0602] The components (x3-1) to (x3-4) constituting the sizing agent used when producing the fibrous reinforcing material are as follows.
[0603] (x3-1) Polyurethane resin emulsion
[0604] Trade name: VONDIC (registered trademark) 1050 (manufactured by Dainippon Ink Co., Ltd.)
[0605] (solid content 50% by mass aqueous solution)
[0606] (x3-2) Maleic anhydride copolymer emulsion
[0607] Product name: ACROBINDER (registered trademark) BG-7 (manufactured by Sanyo Chemical Industries, Ltd.)
[0608] (solid content 25% by mass aqueous solution)
[0609] (x3-3) Aminosilane coupling agent
[0610] Trade name: KBE-903 (manufactured by Shin-Etsu Chemical Co., Ltd.)
[0611] γ-Aminopropyltriethoxysilane
[0612] (x3-4) Lubricant
[0613] Product name: Carnauba wax (manufactured by Kato Yoko Co., Ltd.)
[0614] [Production Example 3-4]
[0615] (Manufacture of glass fiber B3-2)
[0616] Glass fiber B3-2 (chopped strands, hereinafter also referred to as "(B3-2)") was obtained by the same method as in the above-mentioned manufacturing example 3-3, except that glass fiber (containing boron oxide) having a number average fiber diameter of 5 μm was used instead of glass fiber (containing boron oxide) having a number average fiber diameter of 7 μm. The amount of glass fiber sizing agent attached to the glass fiber was 0.7% by mass.
[0617] [Production Example 3-5]
[0618] (Manufacture of glass fiber B3-3)
[0619] Glass fiber B3-3 (chopped strands, hereinafter also referred to as "(B3-3)") was obtained by the same method as in the above-mentioned manufacturing example 3-3, except that glass fiber (not containing boron oxide) having a number average fiber diameter of 7 μm was used instead of glass fiber (containing boron oxide) having a number average fiber diameter of 7 μm. The amount of glass fiber sizing agent attached to the glass fiber was 0.6% by mass.
[0620] [Production Example 3-6]
[0621] (Manufacture of glass fiber B3-4)
[0622] Glass fibers B3-4 (chopped strands, hereinafter also referred to as "(B3-4)") were obtained by the same operation as in Manufacturing Example 3-3, except that glass fibers (containing boron oxide) having a number average fiber diameter of 10 μm were used instead of glass fibers (containing boron oxide) having a number average fiber diameter of 7 μm. The amount of the glass fiber sizing agent attached to the glass fibers was 0.5% by mass.
[0623] 3. Other raw materials
[0624] In addition to the above-mentioned raw materials, the following raw materials were used.
[0625] (C3) Ingredients: Copper compounds
[0626] Cuprous iodide: Cuprous iodide (I), manufactured by Wako Pure Chemical Industries, Ltd.
[0627] (D3) Ingredients: Metal halide
[0628] Potassium iodide: Potassium iodide, manufactured by Wako Pure Chemical Industries, Ltd.
[0629] <Production of thermoplastic resin composition>
[0630] [Example 3-1]
[0631] (Production of Thermoplastic Resin Composition PA-a8)
[0632] (1) Melt-kneading process
[0633] A twin-screw extruder (manufactured by Coperion Corporation, trade name "ZSK26MC") with a screw diameter of 26 mm was used. According to the formulation described in Table 20, a mixture obtained by adding a copper compound and a metal halide to the polyamide A3-1 obtained in Preparation Example 3-1 was fed in a top feeding manner, and the glass fiber B3-1 obtained in Preparation Example 3-3 was fed in a side feeding manner. Melt kneading was carried out under extrusion conditions of a set temperature of 290°C, a screw speed of 300 rpm, and a discharge rate of 25 kg / hour, and melt-kneaded pellets were obtained by a strand cutting method. The VN and water content of the obtained melt-kneaded pellets are as described in Table 25.
[0634] (2) Heating process (solid phase polymerization)
[0635] 10 kg of the pellets obtained in the "(1) melt kneading step" were placed in a conical belt vacuum dryer (manufactured by Ohkawara Seisakusho Co., Ltd., trade name RIBOCONE RM-10V), and then 50 g of water was added while stirring, and nitrogen substitution was performed sufficiently (oxygen concentration was 4.2 ppm). While nitrogen was allowed to flow at 2 L / min, the pellets were heated at a temperature of 190° C. for 6 hours while stirring. Then, the temperature was lowered while nitrogen was allowed to flow, and when the temperature reached about 50° C., the pellets were taken out from the device in the form of pellets, thereby obtaining pellets of the thermoplastic resin composition PA-a8. The VN of the obtained pellets is shown in Table 25.
[0636] [Example 3-2]
[0637] (Production of Thermoplastic Resin Composition PA-a9)
[0638] Solid phase polymerization was carried out in the same manner as in Example 3-1, except that the pellets (melt-kneaded product) obtained in the "(1) melt-kneading step" of Example 3-1 were used, 10 g of water was added, and the pellets were heated at a pellet temperature of 190° C. for 6 hours, thereby obtaining pellets of a thermoplastic resin composition PA-a9. The VN of the obtained pellets is shown in Table 25.
[0639] [Example 3-3]
[0640] (Production of Thermoplastic Resin Composition PA-a10)
[0641] Solid phase polymerization was carried out in the same manner as in Example 3-1, except that the pellets (melt-kneaded product) obtained in the "(1) melt-kneading step" of Example 3-1 were used, 80 g of water was added, and the pellets were heated at a pellet temperature of 190° C. for 6 hours, thereby obtaining pellets of the thermoplastic resin composition PA-a10. The VN of the obtained pellets is shown in Table 25.
[0642] [Examples 3-4]
[0643] (Production of Thermoplastic Resin Composition PA-a11)
[0644] The pellets (melt-kneaded product) obtained in the "(1) melt-kneading step" of Example 3-1 were left to stand for 5 days at room temperature of 23°C and humidity of 60% to absorb water. The water content after water absorption was 0.5% by weight. The pellets after water absorption were heated at a pellet temperature of 190°C for 6 hours, and solid-phase polymerization was performed in the same manner as in Example 3-1 to obtain pellets of the thermoplastic resin composition PA-a10. The VN of the obtained pellets is shown in Table 25.
[0645] [Examples 3-5]
[0646] (Production of Thermoplastic Resin Composition PA-a12)
[0647] Solid phase polymerization was carried out in the same manner as in Example 3-1, except that the pellets (melt-kneaded product) obtained in the "(1) melt-kneading step" of Example 3-1 were used, 50 g of water was added, and the pellets were heated at a pellet temperature of 210° C. for 9 hours, thereby obtaining pellets of the thermoplastic resin composition PA-a12. The VN of the obtained pellets is shown in Table 26.
[0648] [Examples 3-6 to 3-9]
[0649] (Production of Thermoplastic Resin Compositions PA-a13 to PA-a16)
[0650] Except that the composition described in Tables 21 and 22 was used in the "(1) Melt-kneading step" of Example 3-1, melt-kneading was carried out in the same manner as in Example 3-1. The VN and water content of the obtained pellets are shown in Tables 26 and 27. Next, solid phase polymerization was carried out in the same manner as in Example 3-1 to obtain pellets of thermoplastic resin compositions PA-a13 to PA-a16. The VN of the obtained pellets is shown in Tables 26 and 27.
[0651] In addition, in the thermoplastic resin composition of Example 3-9, the mass ratio of boron oxide was 0 mass % relative to 100 mass % of the thermoplastic resin composition.
[0652] [Example 3-10]
[0653] (Production of Thermoplastic Resin Composition PA-a17)
[0654] Except that the composition described in Table 22 was used in the "(1) Melt-kneading step" of Example 3-1, melt-kneading was carried out in the same manner as in Example 3-1. The VN and moisture content of the obtained pellets are as described in Table 27. Next, solid-phase polymerization was carried out in the same manner as in Example 3-1, except that the pellets were heated at a pellet temperature of 190° C. for 3 hours, thereby obtaining pellets of the thermoplastic resin composition PA-a17. The VN of the obtained pellets is as described in Table 27.
[0655] [Comparative Example 3-1]
[0656] (Production of Thermoplastic Resin Composition PA-b3)
[0657] Solid phase polymerization was carried out in the same manner as in Example 3-1, except that the pellets (melt-kneaded product) obtained in the "(1) melt-kneading step" of Example 3-1 were heated at a pellet temperature of 190° C. for 6 hours without adding water, thereby obtaining pellets of a polyamide resin composition PA-b3. The VN of the obtained pellets is shown in Table 28.
[0658] [Comparative Example 3-2]
[0659] (Production of Thermoplastic Resin Composition PA-b4)
[0660] Solid phase polymerization was carried out in the same manner as in Example 3-1, except that the pellets (melt-kneaded product) obtained in the "(1) melt-kneading step" of Example 3-1 were used, 1 g of water was added, and the pellets were heated at a pellet temperature of 190° C. for 6 hours, thereby obtaining pellets of a thermoplastic resin composition PA-b4. The VN of the obtained pellets is shown in Table 28.
[0661] [Comparative Examples 3-3 to 3-4]
[0662] (Production of Thermoplastic Resin Compositions PA-b5 to PA-b6)
[0663] Except that the composition described in Table 23 was changed in the "(1) melt kneading step" of Example 3-1, melt kneading was carried out in the same manner as in Example 3-1. The VN and water content of the obtained pellets are as described in Table 28. Next, solid phase polymerization was carried out in the same manner as in Example 3-1 to obtain pellets of thermoplastic resin compositions PA-b5 to PA-b6. The VN of the obtained pellets is as described in Table 28.
[0664] [Comparative Examples 3-5]
[0665] (Production of Thermoplastic Resin Composition PA-b7)
[0666] Melt kneading was carried out in the same manner as in Example 3-1 except that the "(1) melt kneading step" of Example 3-1 was changed to the formulation described in Table 24. However, the cutting property by the strand cutting method was poor and no pellets were obtained. Therefore, the subsequent heating step (solid phase polymerization) was not carried out.
[0667] [Comparative Examples 3-6]
[0668] (Production of Thermoplastic Resin Composition PA-b8)
[0669] Except that the composition described in Table 24 was used in the "(1) Melt-kneading step" of Example 3-1, melt-kneading was carried out in the same manner as in Example 3-1. The VN and water content of the obtained pellets are shown in Table 29. Next, solid-phase polymerization was carried out in the same manner as in Example 3-1, except that the pellets were heated at a temperature of 190° C. for 6 hours without adding water, thereby obtaining pellets of the thermoplastic resin composition PA-b8. The VN of the obtained pellets is shown in Table 29.
[0670] [Comparative Examples 3-7]
[0671] (Production of Thermoplastic Resin Composition PA-b9)
[0672] Except that the blending composition described in Table 24 was changed in the "(1) melt kneading step" of Example 3-1, melt kneading was carried out in the same manner as in Example 3-1. The VN and water content of the obtained pellets are shown in Table 29. Next, solid phase polymerization was carried out in the same manner as in Example 3-1 to obtain pellets of the thermoplastic resin composition PA-b9. The VN of the obtained pellets is shown in Table 29.
[0673] [Table 20]
[0674]
[0675] [Table 21]
[0676]
[0677] [Table 22]
[0678]
[0679] [Table 23]
[0680]
[0681] [Table 24]
[0682]
[0683] [Table 25]
[0684]
[0685] [Table 26]
[0686]
[0687] [Table 27]
[0688]
[0689] [Table 28]
[0690]
[0691] [Table 29]
[0692]
[0693] As can be seen from Table 1, all evaluation items of the polyamide resin compositions PA-a8 to PA-a17 (Examples 3-1 to 3-10) were good.
[0694] Industrial Applicability
[0695] The fiber-reinforced polyamide resin composition of the first embodiment and the molded body of the second embodiment of the present invention have excellent mechanical properties, reduced property variations, and excellent wear characteristics, and therefore have industrial applicability in the automotive field, electrical and electronic field, mechanical and industrial field, office equipment field, aviation and aerospace field, etc.
[0696] According to the method for producing a thermoplastic resin composition of the third embodiment of the present invention, a thermoplastic resin composition having excellent physical properties and production cost can be obtained. The thermoplastic resin composition obtained by the present invention is suitable for use in, for example, automobile parts, electronic and electrical parts, industrial machinery parts, various gears, etc.
[0697] According to the method for producing a thermoplastic resin composition of the fourth embodiment of the present invention, a thermoplastic resin composition having excellent color tone and vibration fatigue resistance can be obtained. The thermoplastic resin composition obtained by the present invention is suitable for use in, for example, automobile parts, electronic and electrical parts, industrial machinery parts, various gears, etc.
Claims
1. A fiber-reinforced polyamide resin composition, comprising a crystalline polyamide (A1) and a glass fiber (B1), wherein: The fiber-reinforced polyamide resin composition has a formic acid relative viscosity of 90 or more, When the fiber-reinforced polyamide resin composition is dissolved in formic acid, the insoluble content relative to the ash content of the fiber-reinforced polyamide resin composition is 105 mass % or more, The ratio of glass fibers having a fiber length of 250 μm or less in the glass fibers (B1) contained in the fiber-reinforced polyamide resin composition is 55% or less.
2. The fiber-reinforced polyamide resin composition according to claim 1, wherein The glass fibers have a number average fiber diameter of 5 μm or more and 9 μm or less.
3. The fiber-reinforced polyamide resin composition according to claim 1, wherein The fiber-reinforced polyamide resin composition contains 1 part by mass or more and 100 parts by mass or less of the glass fiber (B1) based on 100 parts by mass of the crystalline polyamide (A1).
4. The fiber-reinforced polyamide resin composition according to claim 1, wherein The fiber-reinforced polyamide resin composition has a formic acid relative viscosity of 130 or more.
5. A molded body, wherein The molded product is obtained by molding the fiber-reinforced polyamide resin composition according to any one of claims 1 to 4.
6. A sliding member, wherein: The sliding member comprises the fiber-reinforced polyamide resin composition according to any one of claims 1 to 4.
7. The sliding member according to claim 6, wherein: The coefficient of variation of the tensile strength of the sliding member measured in accordance with ISO527 is 1.0 or less.
8. A gear, wherein: The gear comprises the fiber-reinforced polyamide resin composition according to any one of claims 1 to 4.
9. A worm gear, wherein: The worm wheel comprises the fiber-reinforced polyamide resin composition according to any one of claims 1 to 4.
10. A method for producing a thermoplastic resin composition, characterized in that: The manufacturing method comprises the following steps: a melt-kneading step of adding 5 parts by mass or more and 100 parts by mass or less of glass fibers having an average fiber diameter of 3 μm or more and 15 μm or less to 100 parts by mass of a thermoplastic resin having a viscosity number RV of 25 or more and 70 or less, and melt-kneading the mixture to obtain a melt-kneaded product; and A heating step, wherein the melt-kneaded product is heated at a temperature T represented by the following formula (I), thereby obtaining a thermoplastic resin composition; The melt-kneaded product is an elliptical columnar pellet having an elliptical columnar shape, and the ratio a / b of the major diameter a to the minor diameter b of the cross section of the elliptical columnar pellet is 1.3 to 3.
0. In the heating step, the elliptical columnar pellets are heated while being stirred. Tm-130℃≤T≤Tm-10℃ (I) (wherein Tm is the melting point of the thermoplastic resin).
11. The method for producing a thermoplastic resin composition according to claim 10, wherein: The thermoplastic resin composition has a viscosity number RV of 70 or more and 400 or less.
12. The method for producing a thermoplastic resin composition according to claim 10 or 11, wherein: In the heating step, heating is performed at the temperature T for 30 minutes to 15 hours.
13. The method for producing a thermoplastic resin composition according to claim 10 or 11, wherein: The thermoplastic resin is polyamide or polyester.
14. The method for producing a thermoplastic resin composition according to claim 13, wherein: The polyamide is at least one selected from the group consisting of polyamide 6, polyamide 66, polyamide 46, polyamide 610, and polyamide 612.
15. The method for producing a thermoplastic resin composition according to claim 10 or 11, wherein: In the heating step, heating at the temperature T is performed in an inert gas atmosphere having an oxygen concentration of 5 ppm or less.
16. The method for producing a thermoplastic resin composition according to claim 10 or 11, wherein: In the heating step, heating at the temperature T is performed in an inert gas atmosphere having a water concentration of 10 ppm or less.
17. A method for producing a thermoplastic resin composition, characterized in that: The manufacturing method comprises the following steps: a melt-kneading step of adding 5 parts by mass or more and 100 parts by mass or less of glass fibers having an average fiber diameter of 3 μm or more and 9 μm or less to 100 parts by mass of a thermoplastic resin having a viscosity number VN of 80 or more and 200 or less, and melt-kneading the mixture to obtain a melt-kneaded product; and a heating step, wherein the melt-kneaded product is heated at a temperature T represented by the following formula (I) to obtain a thermoplastic resin composition, In the heating step, 0.05% by mass to 1.0% by mass of water is contained relative to 100% by mass of the melt-kneaded product obtained in the melt-kneading step. Tm-130℃≤T≤Tm-10℃ (I) (wherein Tm is the melting point of the thermoplastic resin).
18. The method for producing a thermoplastic resin composition according to claim 17, wherein: The thermoplastic resin composition has a viscosity number VN of 200 or more and 350 or less.
19. The method for producing a thermoplastic resin composition according to claim 17 or 18, wherein: The average fiber length of the glass fibers contained in the thermoplastic resin composition after the heating step is 100 μm or more and 1000 μm or less.
20. The method for producing a thermoplastic resin composition according to claim 17 or 18, wherein: The glass fibers have an average fiber diameter of 4 μm or more and 8 μm or less.
21. The method for producing a thermoplastic resin composition according to claim 17 or 18, wherein: In the heating step, heating is performed at the temperature T for 30 minutes to 15 hours.
22. The method for producing a thermoplastic resin composition according to claim 17 or 18, wherein: In the heating step, heating at the temperature T is performed in an inert gas atmosphere having an oxygen concentration of 5 ppm or less.
23. The method for producing a thermoplastic resin composition according to claim 17 or 18, wherein: The thermoplastic resin is polyamide or polyester.
24. The method for producing a thermoplastic resin composition according to claim 23, wherein: The polyamide is polyamide 6, polyamide 66 or polyamide 610.
25. The method for producing a thermoplastic resin composition according to claim 17 or 18, wherein: The thermoplastic resin composition contains substantially no boron oxide.
Citation Information
Patent Citations
Resin composition
JP1987185747A
Resin composition for sliding material
JP1989110558A
Resin composition
JP1996041246A
Continuous solid-phase polymerization of nylon 66, apparatus for continuous solid-phase polymerization and nylon 66 fiber
JP2000198841A
Reduction gear for electric power steering device
JP2003083423A